Positive electrode material and preparation method thereof, positive electrode, sodium battery and electric device
By doping low-content Zn elements into the layered oxide positive electrode material or co-doping with other doped metal elements, the problem of poor structural stability of layered oxides during sodium delamination is solved, and the effect of improving the cycle stability of reversible capacity is achieved.
Patent Information
- Application Number
- CN202410222045.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-28
- Filing Date
- 2024-02-28
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-02-28
AI Technical Summary
The existing layered oxide positive electrode materials have poor structural stability during the de-embedding process, resulting in severe attenuation of its reversible capacity during the cycle, which in turn leads to rapid cycling attenuation of sodium ion batteries.
By doping the transition metal layer with a low content of Zn or Zn elements in the layered oxide and co-doping with other doped metal elements, the arrangement between the metal elements is adjusted, the Jahn-Teller effect is suppressed, and structural stability is improved.
The structural stability of the layered oxide and the cycle stability of the reversible capacity are significantly improved, and the cycle life of the sodium ion battery is extended.
Smart Images

Figure CN119764357A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of sodium batteries, and specifically relates to a positive electrode material and a preparation method thereof, a positive electrode, a sodium battery and an electrical device. Background Art
[0002] Sodium-ion batteries have the advantages of abundant raw material reserves, low price, relatively stable chemical properties and good safety, and are expected to replace lithium-ion batteries in the market. With the continuous development of new energy vehicles and the increasing proportion of clean energy, higher requirements are placed on the energy density and cycle stability of sodium-ion batteries.
[0003] Among the positive electrode materials for sodium ion batteries, layered oxides have become one of the research hotspots due to their relatively high energy density. However, the structural stability of layered oxides is poor, and they are prone to phase change during the process of sodium insertion and extraction, resulting in structural deformation, which causes the reversible capacity of layered oxides to decay severely during the cycle, thus causing the sodium ion battery to decay rapidly during the cycle. Summary of the invention
[0004] In view of the above problems, the present application provides a positive electrode material and a preparation method thereof, a positive electrode containing the positive electrode material, and a sodium battery containing the positive electrode, so as to solve the technical problem that the existing layered oxides have poor structural stability, resulting in rapid attenuation of their own specific capacity and battery cycle.
[0005] In a first aspect, an embodiment of the present application provides a positive electrode material. The positive electrode material of the embodiment of the present application includes a layered oxide as shown in the following chemical formula:
[0006] Na q Ni x Mn y Fe z Zn p M i O j ;
[0007] Among them, 0.8≤q≤1; 0.1≤x≤0.3, 0.2≤y≤0.5, 0.2≤z≤0.35, 0.02≤p≤0.075, 0≤i≤0.1, 1.8≤j≤2, and x+y+z+p+i≤1; M is an active and / or inert doping metal element.
[0008] The layered oxide contained in the positive electrode material of the present application embodiment is a transition metal layer (TMO) containing Ni, Fe, and Mn elements by Zn element or Zn element and the doping metal element shown in M. 6) and controlling the Zn element to the above low content can inhibit the Jahn-Teller effect of the layered oxide itself due to the Mn and Ni elements shown in the chemical formula, and effectively adjust the transition metal layer (TMO 6 ) can significantly reduce the structural distortion and irreversible phase change of the layered oxide shown in the chemical formula during the sodium extraction and insertion process, and can significantly improve the structural stability of the layered oxide, so as to significantly improve the cycle stability of the reversible capacity of the layered oxide. Furthermore, by controlling the content ratio of each metal element, on the basis of effectively improving the structural stability of the layered oxide, the gram capacity of the layered oxide can be further improved. Furthermore, low-content Zn elements can also significantly reduce the segregation of transition metal elements on the surface of the layered oxide shown in the chemical formula, improve the air stability of the layered oxide shown in the chemical formula in the air, avoid slurry agglomeration and gelation, improve the electrical properties and improve the processing performance of the layered oxide shown in the chemical formula.
[0009] In some embodiments, at least one of q, x, y, z, p and i is in the following value range: 0.15≤x≤0.25, 0.25≤y≤0.45, 0.25≤z≤0.32, 0.04≤p≤0.07, 0≤i≤0.05.
[0010] By further selecting and controlling the stoichiometric ratio of at least one element among Na, Ni, Mn, Fe, Zn and M within this range, the doping of the transition metal layer in the layered oxide shown in the chemical formula by the Zn element or the doping metal element shown in Zn element and M can be further improved, so as to further adjust the arrangement between the metal elements in the transition metal layer, thereby further improving the structural stability of the layered oxide shown in the chemical formula during the process of sodium insertion and deinsertion, and improving the specific capacity of the layered oxide and the cyclic stability of the reversible capacity.
[0011] In some embodiments, the stoichiometric ratio of the total stoichiometric ratio of Ni, Mn, Fe, Zn and the doping metal element to the stoichiometric ratio of the Na element is 1:(0.8-1), and can be optionally 1:(0.83-0.95).
[0012] By controlling the stoichiometric ratio of the Na element to other metal elements contained in the layered oxide represented by the chemical formula within this range, the cycle stability of the specific capacity and reversible capacity of the layered oxide can be further improved.
[0013] In some embodiments, the stoichiometric ratio of the Zn element to the Ni element is 1:(3-15), and can be optionally 1:(3.1-11).
[0014] The stoichiometric ratio of the Zn element to the Ni element is controlled within this range. The stoichiometric ratio of the Zn element to the Ni element within this range can reduce the cost while increasing the gram capacity of the layered oxide represented by the chemical formula.
[0015] In some embodiments, the stoichiometric ratio of the Zn element to the Mn element is 1:(4-25), and can be optionally 1:(5-15).
[0016] By controlling the stoichiometric ratio of Zn to Mn within this range, it is possible to increase the gram capacity while regulating the Jahn-Teller effect in which Mn participates in the transition metal layer, further reducing the structural distortion and irreversible phase transition of the layered oxide shown in the chemical formula during the sodium insertion and extraction process, thereby further improving the structural stability of the layered oxide.
[0017] In some embodiments, the doping metal element includes at least one of V, Ca, Cr, Al, Sc, Sn, Sb, Zr, Nb, Ti, Mg, Cu, Ru, and Ir. The doping metal element M can further dope the transition metal layer contained in the layered oxide shown in the chemical formula together with a low content of Zn element, adjust the arrangement of the metal elements in the transition metal layer, and according to the type of the doping metal element M, further improve the structural stability and / or gram capacity of the layered oxide shown in the chemical formula during the sodium insertion and extraction process.
[0018] In some embodiments, the layered oxide includes Na 0.89 Ni 0.23 Mn 0.45 Fe 0.3 Zn 0.02 O 2 、Na 0.89 Ni 0.23 Mn 0.44 Fe 0.3 Zn 0.03 O 2 、Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Cu 0.02 O 2 、Na 0.89 Ni 0.23 Mn 0.42 Fe 0.3 Zn 0.05 O 2 、Na 0.89 Ni 0.23 Mn 0.41 Fe 0.3 Zn 0.06 O 2 、Na0.89 No 0.23 Mn 0.42 Fe 0.285 Zn 0.065 ABOUT 2 ,On 0.89 No 0.23 Mn 0.42 Fe 0.28 Zn 0.07 ABOUT 2 、 On 0.9 No 0.23 Mn 0.4 Fe 0.3 Zn 0.075 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 V 0.02 ABOUT 2 、 On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Cr 0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Al 0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Sc 0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Sn 0.02 ABOUT 2 、 On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Sat 0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Zr 0.02 ABOUT2 、 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Nb 0.02 O 2 、Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ti 0.02 O 2 、 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Mg 0.02 O 2 、Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ru 0.02 O 2 、 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ir 0.02 O 2 、Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ir 0.02 O 1.8 At least one of .
[0019] The layered oxide shown in the chemical formula has a low Zn content, and the low Zn content works together with other metal elements to form a specific arrangement between the metal elements in the transition metal layer contained in the layered oxide, thereby further improving the structural stability of the layered oxide during the sodium insertion and extraction process, and improving the cycle stability of the specific capacity and reversible capacity of the layered oxide. At the same time, on the basis of being able to improve the specific capacity of the layered oxide shown in the chemical formula, the electrochemical performance and processing performance can be improved.
[0020] In some embodiments, the layered oxide includes at least one of the following features (1) to (3):
[0021] (1) The crystal structure includes an O3 phase layered metal oxide, and the O3 phase layered metal oxide accounts for more than 95% of the total weight of the layered oxide;
[0022] (2) Dv50 particle size is 3 to 11 μm, and can be 4 to 8 μm;
[0023] (3) It includes a single crystal, wherein the single crystal has a flat morphology.
[0024] In an embodiment, the characteristics of the single crystal include at least one of the following (1) to (4):
[0025] (1) The ratio of length, width and thickness is 1-8:1-5:0.5-2.5, which can be 2-6:2-4:1-2;
[0026] (2) Length is 1 to 8 μm, and can be 2 to 6 μm;
[0027] (3) Width is 1 to 5 μm, and can be 2 to 4 μm;
[0028] (4) The thickness is 0.5 to 2.5 μm, and can be optionally 1 to 2 μm.
[0029] The layered oxides shown in the chemical formulas in the above embodiments are mainly O3 phase layered metal oxides and include a single crystal structure.
[0030] In some embodiments, the layered oxide includes at least one of the following features (1) to (3):
[0031] (1) The compaction density under 2 tons of pressure is 2.8 to 3.1 g / cm 3 , optional: 2.9~3.09g / cm 3 ;
[0032] (2) The compaction density under 3 tons of pressure is 3.1-3.3 g / cm 3 , can be selected as 3.15~3.28g / cm 3 ;
[0033] (3) Specific surface area is 0.5 to 1.3 m 2 / g, optional range is 0.6~0.9m 2 / g.
[0034] Based on the Dv50 particle size of the layered oxide shown in the above chemical formula (I) and the size distribution range of the O3 phase layered metal oxide single crystals contained therein, the layered oxide has a high compaction density, thereby improving the energy density of the battery; at the same time, the layered oxide has a suitable specific surface area, which can improve the stability of the contact interface between the layered oxide and the electrolyte and other properties, thereby improving the electrochemical properties such as the cycle performance.
[0035] In some embodiments, the layered oxide comprises at least one of the following (1) to (3) at 1.5 to 4.2 V and 0.1 C:
[0036] (1) The charging capacity is 164-174 mAh / g, and can be selected as 165-172 mAh / g;
[0037] (2) The discharge capacity is 158-165 mAh / g, and can be selected as 160-163 mAh / g;
[0038] (3) The initial efficiency is 92-98%, which can be selected as 92-95%.
[0039] The structural stability of the layered oxide shown in the above chemical formula has been significantly improved, the structural stability in the process of sodium insertion and extraction, high gram capacity, and good cyclic stability of reversible capacity.
[0040] In a second aspect, the present invention provides a method for preparing a positive electrode material. The method for preparing a positive electrode material in the present invention comprises the following steps:
[0041] Provides Na q Ni x Mn y Fe z Zn p M i O j Precursor of
[0042] The precursor is sintered to obtain a product having a chemical formula of Na q Ni x Mn y Fe z Zn p M i O j Layered oxides;
[0043] Among them, 0.8≤q≤1; 0.1≤x≤0.3, 0.2≤y≤0.5, 0.2≤z≤0.35, 0.02≤p≤0.075, 0≤i≤0.1, 1.8≤j≤2, and x+y+z+p+i≤1; M is an active and / or inert doping metal element.
[0044] The positive electrode material preparation method of the present application embodiment is to q Ni x Mn y Fe z Zn p M i O j The precursor is sintered to generate a chemical formula of Na q Ni x Mn y Fe z Zn p M i Oj Therefore, the layered oxide prepared by the positive electrode material preparation method of the present application embodiment has a low zinc content and high structural stability during the sodium insertion and extraction process, so that the prepared layered oxide has a high gram capacity and a cyclic stability of its reversible capacity. At the same time, it also has high air stability and diffusion rate. In addition, for Na q Ni x Mn y Fe z Zn p M i O j The sintering conditions of the precursor can be effectively controlled, thereby improving the q Ni x Mn y Fe z Zn p M i O j The stability of the structure and electrochemical properties of layered oxides.
[0045] In some embodiments, the doping metal element includes at least one of V, Ca, Cr, Al, Sc, Sn, Sb, Zr, Nb, Ti, Mg, Cu, Ru, and Ir. These doping metal elements can further dope the transition metal layer contained in the layered oxide shown in the chemical formula together with a low content of Zn element, adjust the arrangement of the metal elements in the transition metal layer, and further improve the structural stability and / or gram capacity of the layered oxide shown in the chemical formula during the sodium insertion and extraction process according to the type of the doping metal element.
[0046] In some embodiments, at least one of q, x, y, z, p and i is in the following value range:
[0047] 0.15≤x≤0.25, 0.25≤y≤0.45, 0.25≤z≤0.32, 0.04≤p≤0.07, 0≤i≤0.05.
[0048] By adding Na q Ni x Mn y Fe z Zn p M i O j The ratio of these metal elements in the precursor is further controlled within this range, which can further adjust the arrangement of the metal elements in the prepared layered oxide, thereby further improving the structural stability of the prepared layered oxide during the process of sodium insertion and deinsertion, and improving the specific capacity of the layered oxide and the cyclic stability of the reversible capacity.
[0049] In some embodiments, the sintering process includes at least one of the following conditions (1) to (4):
[0050] (1) The temperature is 700-980°C, and can be 750-950°C;
[0051] (2) The time is 4 to 20 hours, and can be 6 to 12 hours;
[0052] (3) The temperature is raised to the sintering temperature at a heating rate of 2 to 15°C / min.
[0053] By controlling the sintering conditions within the above range, the Na q Ni x Mn y Fe z Zn p M i O j The structural stability of the layered oxide during the sodium insertion and extraction process further improves the high specific capacity of the layered oxide and the cycle stability of its reversible capacity. q Ni x Mn y Fe z Zn p M i O j The content of O3 phase layered metal oxide and the single crystal content in the layered oxide control the single crystal size and the particle size of the layered oxide, thereby increasing the compaction density of the layered oxide.
[0054] In some embodiments, the Na q Ni x Mn y Fe z Zn p M i O j The precursor is prepared according to a method comprising the following steps:
[0055] According to Na q Ni x Mn y Fe z Zn p M i O j The precursor is obtained by solid phase mixing the sodium source, nickel source, manganese source, iron source, zinc source and the doping metal element source shown in M according to the stoichiometric ratio of the elements contained.
[0056] The solid phase method was used to prepare Na q Ni x Mn y Fe z Znp M i O j The precursor can effectively control the stoichiometric ratio of each element and improve the preparation effect of the precursor.
[0057] In some embodiments, the Na q Ni x Mn y Fe z Zn p M i O j The precursor is prepared according to a method comprising the following steps:
[0058] According to Na q Ni x Mn y Fe z Zn p M i O j A soluble nickel source, a soluble manganese source, a soluble iron source, a soluble zinc source and a soluble doping metal element source represented by M are prepared into a mixed solution according to the stoichiometric ratio of the elements, and at least one of a precipitant and a complexing agent is added to perform a coprecipitation treatment to obtain a precipitated mixture;
[0059] The precipitation mixture is mixed with a sodium source to obtain the precursor.
[0060] The coprecipitation method was used to prepare Na q Ni x Mn y Fe z Zn p M i O j The precursor can improve the stoichiometric ratio accuracy of each element.
[0061] In a third aspect, the present invention provides a positive electrode, which includes a current collector and a positive electrode active material layer combined with the current collector, wherein the positive electrode active material layer includes the positive electrode material of the present invention or the positive electrode material prepared by the positive electrode material preparation method of the present invention.
[0062] Since the positive electrode active material layer of the positive electrode of the embodiment of the present application contains the positive electrode material of the embodiment of the present application, the positive electrode has a relatively high gram capacity and good cycle performance.
[0063] In some embodiments, the content of the positive electrode active material layer on the single surface of the current collector is 260-350 mg / 1540.25 mm 2 , optional: 280~320mg / 1540.25mm 2The positive electrode active material layer within this content range can effectively increase the gram capacity of the positive electrode and thus increase the energy density of the battery.
[0064] In some embodiments, the compaction density of the positive electrode active material layer is 2.8 to 3.4 g / cm 3 , can be selected as 2.9~3.2g / cm 3 The compaction density in this range can effectively increase the gram capacity of the positive electrode, thereby increasing the energy density of the battery, and the interface stability with the electrolyte is good.
[0065] In some embodiments, the porosity of the positive electrode active material layer is 40% to 65%, and can be 45% to 60%. The porosity in this range enables the positive electrode active material layer to have the above compaction density, thereby increasing the gram capacity of the positive electrode and thus the energy density of the battery, and improving the wettability of the electrolyte.
[0066] In some embodiments, the positive electrode is a pole piece, and the pole piece has a sheet resistance of 0.5 to 5 mΩ, and can be 0.5 to 3 mΩ. The sheet resistance in this range can effectively improve performance including efficiency and lifespan.
[0067] In some embodiments, the positive electrode is a pole piece, and the ratio of the thickness from one surface of the pole piece to the other opposite surface to the thickness of the current collector is 6 to 15:1, and can be optionally 8 to 14:1.
[0068] By controlling the total thickness of the pole piece and the thickness of the current collector within the above ratio range, the gram capacity of the pole piece can be effectively increased, thereby increasing the energy density of the battery, and increasing the bonding strength between the positive electrode active material layer and the current collector, thereby increasing the mechanical strength of the pole piece structure and improving the cycle performance of the pole piece.
[0069] In some embodiments, the conductive agent contained in the positive electrode active material layer includes a linear conductive agent.
[0070] In an embodiment, the mass content of the linear conductive agent in the positive electrode active material layer is 0.1% to 2.5%, and can be optionally 0.2% to 0.8%.
[0071] In the embodiment, the aspect ratio of the linear conductive agent is 40 to 3000:1, and can be optionally 50 to 2500:1.
[0072] In the embodiment, the length of the linear conductive agent is 0.5 to 5 μm, and can be optionally 0.5 to 2 μm.
[0073] In an embodiment, the diameter of the linear conductive agent is 2 to 10 nm, and can be 3 to 7 nm.
[0074] In an exemplary embodiment, the linear conductive agent includes at least one of carbon nanotubes, carbon fibers, and conductive oxide nanowires.
[0075] A linear conductive agent is added to the positive electrode active material layer, and the content of the linear conductive agent is controlled within the range and the type, aspect ratio, length and diameter of the linear conductive agent are selected within the above range, so that the linear conductive agent can form a rich conductive network structure in the positive electrode active material layer, and the linear conductive agent can also be wrapped around the surface of the flat single crystal particles. The granular conductive agent can be effectively dispersed in the gaps of the positive electrode material. In this way, the linear conductive agent constructs a long-range conductive network structure in the positive electrode active material layer, and the granular conductive agent constitutes a short-range conductive structure. Therefore, the conductive synergistic effect of the linear conductive agent and the granular conductive agent in the positive electrode active material layer effectively improves the conductivity of the positive electrode active material layer and can significantly reduce the internal resistance of the positive electrode.
[0076] In a fourth aspect, the present application provides a sodium battery. The sodium battery of the present application includes the positive electrode of the above-mentioned present application.
[0077] Since the sodium battery of the embodiment of the present application contains the positive electrode of the embodiment of the present application, the sodium battery of the embodiment of the present application has high energy density and good cycle performance.
[0078] In a fifth aspect, an embodiment of the present application provides an electrical device, and the embodiment of the present application includes a sodium battery according to an embodiment of the present application.
[0079] The electrical device in the embodiment of the present application has a long standby or battery life and a long service life.
[0080] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0082] Figure 1 A scanning electron microscope (SEM) image of the layered oxide provided in Example A6 of the present application;
[0083] Figure 2 A schematic diagram of the single crystal structure of the layered oxide contained in the positive electrode material of some embodiments of the present application;
[0084] Figure 3 A schematic diagram of the structure of the positive electrode of some embodiments of the present application;
[0085] Figure 4 Another schematic diagram of the structure of the positive electrode of some embodiments of the present application;
[0086] Figure 5 This is a schematic structural diagram of an implementation of a sodium battery cell according to an embodiment of the present application;
[0087] Figure 6 for Figure 5 An exploded schematic diagram of a sodium battery cell is shown;
[0088] Figure 7 This is a schematic structural diagram of an implementation scheme of a battery module according to an embodiment of the present application;
[0089] Figure 8 This is a schematic structural diagram of an implementation scheme of a battery pack according to an embodiment of the present application;
[0090] Fig. 9 for Figure 8 A schematic diagram of the exploded structure of the battery pack shown;
[0091] Fig.10 It is a schematic diagram of an implementation of an electrical device including the battery of an embodiment of the present application as a power source.
[0092] The reference numerals in the specific implementation manner are as follows:
[0093] 10-positive electrode, 11 current collector, 12-positive electrode active material layer;
[0094] 20-battery cell, 21-housing, 22-electrode assembly, 23-cover plate;
[0095] 30-battery module;
[0096] 40 -battery pack, 41 -upper box, 42 -lower box. DETAILED DESCRIPTION
[0097] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0098] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0099] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0100] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0101] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0102] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0103] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0104] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0105] Sodium-ion batteries (SIBs) are ideal candidates for energy storage systems due to their abundant raw material reserves and low price. They also have huge application space in the new energy vehicle market. With the rapid development of energy storage systems and new energy vehicles, the requirements for the energy density and cycle stability of sodium-ion batteries are becoming higher and higher.
[0106] For sodium-ion batteries, the positive electrode material of sodium-ion batteries can provide active sodium ions, which is an important component of sodium-ion batteries and one of the important factors affecting the energy density and cycle performance of sodium-ion batteries. Among the positive electrode materials of sodium-ion batteries, layered oxides have attracted much attention due to their higher gram capacity and structure similar to that of lithium-ion battery positive electrode materials.
[0107] According to the arrangement and stacking order of oxygen atoms in the layered oxide, the layered oxide is currently mainly divided into P2 type and O3 type. 2 / 3 Ni 1 / 3 Mn 2 / 3 O 2 Although it has a high capacity, it is easy to produce P during the process of sodium insertion and extraction. 2 -O 2 Phase transition. This phase transition causes Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O 2 Compared with P2-type layered oxides, O3-type layered oxides can store more Na + , can also exert a higher reversible capacity within the same voltage range, so it has better commercial application prospects. However, Na + The diffusion of O3-type layered oxides such as NaMn 0.5 Ni 0.5 O 2 Layered oxides undergo complex phase transitions during the charge and discharge process, especially the irreversible P3″ phase transition that occurs when charged to a high voltage above 4.1V. This phase transition causes the structural destruction of the O3-type layered oxide, causing its capacity to decay and reducing its cycle life.
[0108] Therefore, the structural stability of the layered oxide is poor at present, and it is easy to undergo phase change during the sodium extraction process, resulting in structural deformation, which causes the reversible capacity of the layered oxide to decay severely during the cycle, thereby causing the sodium ion battery to decay quickly. In order to improve the crystal structure stability of the layered oxide during the sodium extraction process and the electrochemical properties including reversible capacity and cycle performance, it is currently reported that the layered oxide is treated with heterogeneous elements. Although the electrochemical properties such as the crystal structure stability and cycle performance of the layered oxide after doping are improved, they are not obvious. For example, it is generally believed that when the layered oxide is doped with zinc elements, because the zinc element does not participate in the redox reaction of the layered oxide during the charge and discharge process, it can play the role of a stabilizer to reduce the structural distortion and slip phenomenon of the layered oxide during the charge and discharge process, thereby improving the structural stability of the layered oxide to improve its reversible capacity and cycle performance. At the same time, it is generally believed that as the doping amount of the zinc element increases, its role as a stabilizer is also obvious, which can further reduce the structural distortion and slip phenomenon of the layered oxide during the charge and discharge process and improve the structural stability of the layered oxide. Therefore, it is generally believed that controlling the doping amount of zinc element to be high is beneficial to the structural stability of the layered oxide. In the layered oxide, the molar doping amount of zinc element is generally above 8%.
[0109] However, through research, it was unexpectedly discovered that reducing the doping content of zinc can effectively alleviate the premature structural phase change phenomenon of nickel-manganese layered oxides, reduce the phase change of nickel-manganese layered oxides during the charge and discharge process, and significantly improve the crystal structure stability of nickel-manganese layered oxides during the sodium insertion and extraction process, thereby improving the gram capacity and reversible capacity of nickel-manganese layered oxides. Stability during the cycle process. Based on the above research, the following technical solutions are proposed in the embodiments of this application.
[0110] Cathode Materials
[0111] In a first aspect, embodiments of the present application provide a low zinc-doped positive electrode material. In some embodiments, the positive electrode material of the present application embodiment comprises a layered oxide represented by the following chemical formula (I):
[0112] Na q Ni x Mn y Fe z Zn p M i O j (I);
[0113] Wherein, in the chemical formula (I), 0.8≤q≤1, 0.1≤x≤0.3, 0.2≤y≤0.5, 0.2≤z≤0.35, 0.02≤p≤0.075, 0≤i≤0.1, 1.8≤j≤2, and x+y+z+p+i≤1; M is an active and / or inert doping metal element.
[0114] In the chemical formula (I) of the layered oxide contained in the positive electrode material of the embodiment of the present application, q, x, y, z, p, i and j respectively represent the stoichiometric content ratios of the doped metal elements shown in Na, Ni, Mn, Fe, Zn and M and O in the layered oxide. Therefore, the stoichiometric content ratio of Na, Ni, Mn, Fe, Zn, M and O contained in the layered oxide can be 0.8-1: 0.1-0.3: 0.2-0.5: 0.2-0.35: 0.02-0.075: t-0.1: 1.8-2; wherein 0≤t<0.1. In addition, the stoichiometric ratio of the doped metal elements shown in Na, Ni, Mn, Fe, Zn, M and O can be a molar ratio or a mass ratio converted according to the molar ratio. The active doped metal element shown in M refers to a type of metal element that has electrochemical redox activity in the layered oxide and mainly contributes to the gram capacity of the layered oxide. The inert doping metal element M is relative to the active doping metal element, and refers to a type of metal element that is relatively stable in electrochemical redox activity in the layered oxide and mainly contributes to the stability of the layered oxide crystal structure. The layered oxide refers to a transition metal layer (TMO) composed of alternating arrangements of Ni, Mn and Fe elements. 6 ) octahedron and sodium layer (NaO 6 )A positive electrode material composed of an alkali metal layer.
[0115] The layered oxide contained in the positive electrode material of the present application embodiment is a transition metal layer (TMO) containing Ni, Fe, and Mn elements by Zn element or Zn element is further doped with the metal element shown in M. 6) is doped, and the doping amount of Zn element is controlled within the low content range shown in p, so that Zn element and Fe element or Zn element and Fe element and the doped metal element shown in M can jointly participate in the arrangement between the metal elements in the transition metal layer contained in the layered oxide crystal, mainly disordered arrangement, which can inhibit the Jahn-Teller effect brought by Mn element and the structural phase change brought by excessive nickel element of the layered oxide shown in chemical formula (I) itself. Compared with the layered oxide with high content of zinc element at present, it can reduce the structural phase change of the layered oxide shown in chemical formula (I), and can significantly reduce the structural distortion and irreversible phase change of the layered oxide shown in chemical formula (I) during the process of sodium insertion and extraction, and can significantly improve the structural stability of the layered oxide, so as to improve the cycle stability of the reversible capacity of the layered oxide. At the same time, by controlling the content ratio of each metal element, on the basis of effectively improving the structural stability of the layered oxide, the gram capacity of the layered oxide can be further improved. Moreover, the content ratio of each metal element can also effectively adjust the transition metal layer (TMO 6 ) can control the amount of sodium removal, and can also increase the structural distortion and irreversible phase transition of the layered oxide during the sodium insertion and deinsertion process, which can significantly improve the structural stability of the layered oxide.
[0116] Furthermore, the low content of Zn in the layered oxide of the chemical formula (I) can also significantly reduce the segregation of transition metal elements on the surface of the layered oxide of the chemical formula (I), improve the air stability of the layered oxide of the chemical formula (I) in the air, avoid slurry agglomeration and gelation, improve the electrical properties, and improve the processing properties and electrical properties of the layered oxide of the chemical formula (I). In addition, the low content of Zn or Zn further combined with the doping metal element shown in M can significantly reduce the segregation of transition metal elements on the surface of the layered oxide of the chemical formula (I), improve the air stability of the layered oxide of the chemical formula (I), avoid slurry agglomeration and gelation, improve the electrical properties, and improve the processing properties and electrical properties of the layered oxide of the chemical formula (I). 6 ) can effectively inhibit the Na + and vacancies, reducing the Na + The diffusion energy barrier increases the diffusion rate of sodium ions contained in the layered oxide.
[0117] In the exemplary embodiment, in the chemical formula (I) of the layered oxide contained in the positive electrode material of the present embodiment, the stoichiometric content q of the Na element can be a typical but non-limiting stoichiometric content such as 0.8, 0.85, 0.9, 0.95, 1.0, or a range between any two stoichiometric content values. The Na element in this content range increases the reversible capacity of the layered oxide shown in the chemical formula (I).
[0118] In some embodiments, in the chemical formula (I) of the layered oxide contained in the positive electrode material of the embodiment of the present application, the stoichiometric content x of the Ni element can be further 0.15≤x≤0.25. Based on the value range of x in the chemical formula (I), in the exemplary embodiment, x can be a typical but non-restrictive stoichiometric content such as 0.1, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.25, 0.3, or a range between any two stoichiometric content values. On the one hand, the Ni element in this content range can effectively reduce the content of inactive impurity phases such as NiO in the layered oxide under the co-doping of Zn element, Fe element, or Zn element, Fe element, and the doping metal element shown in M, thereby further improving the structural stability of the layered oxide during the sodium deintercalation process. At the same time, Zn element, Fe element, or Zn element, Fe element, and the doping metal element shown in M can also replace part of the Ni element to reduce the content of Ni, thereby reducing the cost of the layered oxide without reducing the gram capacity of the layered oxide shown in the chemical formula (I).
[0119] In some embodiments, in the chemical formula (I) of the layered oxide contained in the positive electrode material of the embodiment of the present application, the stoichiometric content y of the Mn element can be further 0.25≤y≤0.45. Based on the value range of y in the chemical formula (I), in the exemplary embodiment, y can be a typical but non-limiting stoichiometric content such as 0.2, 0.23, 0.25, 0.28, 0.3, 0.33, 0.35, 0.38, 0.4, 0.43, 0.45, 0.48, 0.5, or a range between any two stoichiometric content values. On the one hand, the Mn element in the stoichiometric content range can reduce the Jahn-Teller effect brought by the Mn element and the Ni element under the co-doping of the Zn element, the Fe element, or the doping metal element shown in the Zn element, the Fe element, and the M element, and further improve the structural stability of the layered oxide during the sodium insertion and extraction process; on the other hand, it can also make the layered oxide shown in the chemical formula (I) have a larger average oxidation state and lattice space, thereby increasing the diffusion rate of Na ions.
[0120] In some embodiments, in the chemical formula (I) of the layered oxide contained in the positive electrode material of the embodiment of the present application, the stoichiometric content z of the Fe element can be further 0.25≤z≤0.32. Based on the value range of z in the chemical formula (I), in the exemplary embodiment, z can be a typical but non-restrictive stoichiometric content such as 0.2, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, or a range between any two stoichiometric content values. The Fe element in the stoichiometric content range can be co-doped with the Zn element or the Zn element and the doping metal element shown in M to the transition metal layer in the layered oxide shown in the chemical formula (I), further improving the structural stability of the layered oxide shown in the chemical formula (I) during the sodium deintercalation process; at the same time, the Fe element replaces part of the Ni element, and on the basis of increasing the gram capacity of the layered oxide shown in the chemical formula (I), the content of the Ni element is reduced, and the cost of the layered oxide shown in the chemical formula (I) is reduced.
[0121] In some embodiments, in the chemical formula (I) of the layered oxide contained in the positive electrode material of the present application, the stoichiometric content p of the Zn element can be 0.04≤p≤0.07, and further 0.04≤p≤0.065. Based on the value range of p in the chemical formula (I), in the exemplary embodiment, p can be 0.02, 0.025, 0.025, 0.03, 0.03, 0.035, 0.04, 0.045, 0.045, 0.05, 0.05, 0.055, 0.055, 0.06, 0.06, 0.065, 0.07, 0.075, etc., typical but non-limiting stoichiometric contents or the range between any two stoichiometric content values. The Zn element in the stoichiometric content range can or the Zn element can be further combined with the doping metal element shown in M to improve the doping of the transition metal layer contained in the layered oxide shown in the chemical formula (I), further improve the structural stability of the layered oxide shown in the chemical formula (I) during the sodium insertion and deinsertion process; and at the same time further balance the electrical properties and processing properties of the positive electrode material.
[0122] In some embodiments, in the chemical formula (I) of the layered oxide contained in the positive electrode material of the embodiment of the present application, the stoichiometric content i of the doped metal element shown in M can be further 0≤i≤0.05. Based on the value range of i in the chemical formula (I), in the exemplary embodiment, i can be a typical but non-limiting stoichiometric content such as 0, 0.01, 0.02, 0.03, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a range between any two stoichiometric content values. The doped metal element shown in M in the stoichiometric content range can assist the low-content Zn element to further improve the doping of the transition metal layer contained in the layered oxide shown in the chemical formula (I), adjust the arrangement between the metal elements in the transition metal layer, so as to further improve the structural stability of the layered oxide shown in the chemical formula (I) during the sodium insertion and extraction process, and further improve the cycle stability of its gram capacity and / or reversible capacity.
[0123] In the exemplary embodiment, in the chemical formula (I) of the layered oxide contained in the positive electrode material of the embodiment of the present application, the stoichiometric content j of O can be a typical but non-limiting stoichiometric content such as 1.8, 1.9, 2, or a range between any two stoichiometric content values.
[0124] In an embodiment, the active or / and inert doping metal element shown in M may include at least one of V, Ca, Cr, Al, Sc, Sn, Sb, Zr, Nb, Ti, Mg, Cu, Ru, Ir, etc. Among them, the active doping metal element shown in M may include at least one metal element of V, Ca, Cr, Nb, Cu, Sc, Sn, Sb, etc., and the inert doping metal element shown in M may be at least one metal element of Zr, Mg, Ru, Ir, Al, Ti, etc. Selecting and controlling the active or / and inert doping metal element shown in M to be selected from these elements can further improve the doping of the transition metal layer contained in the layered oxide shown in chemical formula (I) together with the low-content Zn element, adjust the arrangement between the metal elements in the transition metal layer, and according to the type of the doping metal element shown in M, further improve the structural stability and / or gram capacity of the layered oxide shown in chemical formula (I) during the sodium insertion and extraction process.
[0125] Based on the value ranges of q, x, y, z, p, and i in the above embodiments, in some embodiments, the value ranges of q, x, y, z, p, and i in the chemical formula (I) of the layered oxide are as follows:
[0126] 0.8≤q≤1, 0.15≤x≤0.25, 0.25≤y≤0.45, 0.25≤z≤0.32, 0.04≤p≤0.07, 0≤i≤0.05. At this time, the stoichiometric content ratio of the doping metal element represented by Na, Ni, Mn, Fe, Zn and M contained in the layered oxide represented by the chemical formula (I) can be 0.8-1: 0.15-0.25: 0.25-0.45: 0.25-0.32: 0.04-0.065: t-0.05; wherein 0≤t<0.05. By selecting and controlling the stoichiometric ratio of Na, Ni, Mn, Fe, Zn or the doping metal elements shown in Na, Ni, Mn, Fe, Zn and M within this range, the doping of the transition metal layer in the layered oxide shown in the chemical formula (I) by the Zn element or the Zn element and the doping metal element shown in M can be further improved, the structural stability of the layered oxide shown in the chemical formula (I) during the sodium insertion and extraction process can be further improved, the arrangement of the metal elements in the transition metal layer can be adjusted, and the cycle stability of the specific capacity and reversible capacity of the layered oxide can be improved. In addition, the electrochemical properties and processing properties of the layered oxide can be further improved.
[0127] Based on the value ranges of q, x, y, z, p, and i in the above embodiments, in some embodiments, the total stoichiometric ratio of the doping metal elements represented by Ni, Mn, Fe, Zn, and M in the chemical formula (I) of the layered oxide to the stoichiometric ratio of the Na element is 1: (0.8-1), which can be 1: (0.85-0.95), and further 1: (0.85-0.92). In the exemplary embodiment, it can be 1: 0.8, 1: 0.82, 1: 0.85, 1: 0.88, 1: 0.9, 1: 0.95, 1: 1, etc., or the range between any two stoichiometric ratios. The stoichiometric ratio can be the mole number and the mass converted based on the mole number. By controlling the stoichiometric ratio of the Na element to other metal elements contained in the layered oxide represented by the chemical formula (I) within this range, the content of sodium ions can be further increased, the content of sodium ions that can be inserted and extracted in the layered oxide can be increased, and thus the gram capacity of the layered oxide; moreover, the sodium ions in this content range can increase the O3 crystal phase content of the layered oxide represented by the chemical formula (I), so that the layered oxide represented by the chemical formula (I) mainly presents O3 crystals, thereby improving the structural stability of the layered oxide represented by the chemical formula (I) and improving the cyclic stability of its reversible capacity.
[0128] In some embodiments, the stoichiometric ratio of Zn element to Ni element in the chemical formula (I) of the layered oxide is 1:(3-15), which can be optionally 1:(3.1-11). In the exemplary embodiment, it can be a typical but non-limiting molar ratio of 1:3, 1:3.1, 1:5, 1:8, 1:10, 1:11, 1:12, 1:15, etc., or a range between any two stoichiometric ratios. The stoichiometric ratio of the Zn element to the Ni element can be a molar number and a mass converted based on the molar number. The stoichiometric ratio of the Zn element to the Ni element in the chemical formula (I) is controlled within this range. The stoichiometric ratio of the Zn element to the Ni element in this range can further increase the gram capacity of the layered oxide shown in the chemical formula. If it is within the range, appropriately increasing the ratio, that is, appropriately increasing the zinc content, can further increase the gram capacity of the layered oxide shown in the chemical formula.
[0129] In some embodiments, the stoichiometric ratio of the Zn element to the Mn element is 1:(4-25), and can be optionally 1:(5-15). In the exemplary embodiment, it can be a typical but non-limiting stoichiometric ratio of 1:4, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18, 1:20, 1:22, 1:25, or a range between any two stoichiometric ratios. Similarly, the stoichiometric ratio of the Zn element to the Mn element can be a molar number and a mass converted based on the molar number. Controlling the stoichiometric ratio of the Zn element to the Mn element within this range can further adjust the content of Mn in the transition metal layer contained in the layered oxide shown in the chemical formula, thereby further reducing the Jahn-Teller effect between the Mn and Ni elements in the transition metal layer, and further reducing the structural distortion and irreversible phase change of the layered oxide shown in the chemical formula during the sodium insertion and extraction process, so as to further improve the structural stability of the layered oxide. Of course, the above-mentioned stoichiometric ratio range of the Zn element to the Mn element can also take into account the gram capacity of the layered oxide represented by the chemical formula (I).
[0130] In addition, the Zn element and the Ni element and the Zn element and the Mn element in the chemical formula (I) can be controlled in the above stoichiometric ratio range respectively. In one embodiment, they can be controlled in the above stoichiometric ratio range at the same time. At the same time, the stoichiometric ratios of the Zn element and the Ni element and the Zn element and the Mn element are controlled in the above stoichiometric ratio range, so that the layered oxide shown in the chemical formula (I) can better balance the structural stability and gram capacity, that is, the layered oxide shown in the chemical formula (I) has a relatively high gram capacity on the basis of having a better cycle stability of the reversible capacity.
[0131] Based on the value ranges of q, x, y, z, p, and i in the above embodiments, in the embodiments, the layered oxides shown in the chemical formula (I) in the above embodiments may include Na 0.89 Ni 0.23 Mn0.45 Feb 0.3 Zn 0.02 O 2 、So 0.89 Ni 0.23 Mr 0.44 Feb 0.3 Zn 0.03 O 2 、So 0.85 Ni 0.23 Mr 0.42 Feb 0.28 Zn 0.04 Cu 0.02 O 2 、So 0.89 Ni 0.23 Mr 0.42 Feb 0.3 Zn 0.05 O 2 、So 0.89 Ni 0.23 Mr 0.41 Feb 0.3 Zn 0.06 O 2 、So 0.89 Ni 0.23 Mr 0.42 Feb 0.285 Zn 0.065 O 2 、So 0.89 Ni 0.23 Mr 0.42 Feb 0.28 Zn 0.07 O 2 、So 0.9 Ni 0.23 Mr 0.4 Feb 0.3 Zn 0.075 O 2 、 So 0.85 Ni 0.23 Mr 0.42 Feb 0.28 Zn 0.04 V 0.02 O 2 、So 0.85 Ni 0.23 Mr 0.42 Feb 0.28 Zn 0.04 Cr 0.02 O 2 、 So 0.85 Ni 0.23 Mr 0.42 Feb 0.28 Zn 0.04 Al0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Sc 0.02 ABOUT 2 、 On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Sn 0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Sat 0.02 ABOUT 2 、 On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Zr 0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Nb 0.02 ABOUT 2 、 On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 You 0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Mg 0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ru 0.02 ABOUT 2 ,On 0.85 No 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ir 0.02 ABOUT 2 ,On 0.85 No0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ir 0.02 O 1.8 At least one of the above. The layered oxides shown in these chemical formulas have a low content of Zn, and the low content of Zn works together with other metal elements to significantly improve the doping of the transition metal layer contained in the layered oxide shown in chemical formula (I), so that the metal elements in the transition metal layer contained in the layered oxide form a specific arrangement, further improving the structural stability of the layered oxide during the sodium insertion and extraction process, and improving the cyclic stability of the specific capacity and reversible capacity of the layered oxide. At the same time, by controlling the doping content of the Zn element and the Fe element or further with the doped metal element shown in M, the content of the Ni element can also be reduced, and the economic cost of the layered oxide can be reduced on the basis of increasing the specific capacity of the layered oxide shown in chemical formula (I). In addition, the electrochemical properties and processing properties of the layered oxide can be further improved.
[0132] After testing, in some embodiments, the crystal structure of the layered oxide shown in the chemical formula (I) in the above embodiments includes an O3 phase layered metal oxide. Among them, the O3 phase layered metal oxide refers to a layered oxide with a crystal structure in which the oxygen contained therein is stacked in an ABCABC type manner. In the embodiments, the layered oxide shown in the chemical formula (I) in the above embodiments is mainly an O3 phase layered metal oxide. Mainly O3 phase layered metal oxide means that in the layered oxide shown in the chemical formula (I), the weight proportion of the O3 phase layered metal oxide is more than 95% of the total weight of the layered oxide shown in the chemical formula (I), and further more than 98%, of course, including the weight proportion of the O3 phase layered metal oxide in the layered oxide shown in the chemical formula (I) can reach 100%. The higher the weight proportion of the O3 phase layered metal oxide in the layered oxide shown in the chemical formula (I), the more desirable it is. The layered oxide shown in chemical formula (I) mainly exists as O3 phase layered metal oxide or pure O3 phase layered metal oxide, which makes the layered oxide have relatively high structural stability, such as relatively high structural stability relative to P2 phase layered metal oxide, and has higher specific capacity and better cycle stability of reversible capacity.
[0133] In some embodiments, through electron microscopic analysis, the crystals of the layered oxides represented by the chemical formula (I) in the above embodiments include single crystals, which are flat, such as Figure 1 As shown, since the layered oxide is mainly an O3 phase layered metal oxide, the O3 phase layered metal oxide is a single crystal.
[0134] Further electron microscopic analysis of the single crystal revealed that in some embodiments, Figure 2 As shown, the ratio of length L, width W, and thickness H of the single crystal of the layered oxide represented by chemical formula (I) is 1-8:1-5:0.5-2.5, and can be 2-6:2-4:1-2. In the exemplary embodiment, it can be 1:1:0.5, 3:2:0.5, 5:3:1, 7:4:2, 8:5:2.5, 8:2:1, etc., which are typical but non-limiting ratios or ranges between any two ratios. Wherein, the length L and the width W are as follows: Figure 2 L and W are shown in the figure, which are the length L and width W of the large surface of the flat single crystal; the thickness is shown in Figure 2 H in the middle indicates the thickness of a flat single crystal.
[0135] Based on the above-mentioned ratio of length L, width W, and thickness H, in the embodiment, the length L of the single crystal can be 1 to 8 μm, and can be optionally 2 to 6 μm. In the demonstration example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, and other typical but non-restrictive lengths or a range between any two length values.
[0136] In the embodiment, the width W of the single crystal may be 1 to 5 μm, and may be 2 to 4 μm. In the exemplary embodiment, the width W may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or other typical but non-limiting widths, or a range between any two width values.
[0137] In the embodiment, the thickness H of the single crystal can be 0.5-2.5 μm, optionally 1-2 μm. In the exemplary embodiment, it can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm and other typical but non-limiting thicknesses or a range between any two thickness values.
[0138] In the embodiments, after testing, the Dv50 particle size of the layered oxide represented by chemical formula (I) in the above embodiments is 3 to 11 μm, and can be 4 to 8 μm. In the exemplary embodiments, the Dv50 particle size can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, etc., which are typical but non-limiting particle sizes, or the range between any two particle size values. Wherein, the Dv50 particle size refers to the particles of the layered oxide powder represented by chemical formula (I).
[0139] The Dv50 particle size of the layered oxide represented by the chemical formula (I) in the above embodiments and the size distribution range of the single crystal of the O3 phase layered metal oxide contained therein make the layered oxide have a high compaction density, thereby improving the compaction density of the positive electrode material of the embodiment of the present application and improving the energy density of the battery. At the same time, the layered oxide has a suitable specific surface area.
[0140] According to the test, the specific surface area (BET) of the layered oxides represented by the chemical formula (I) in the above embodiments is 0.5 to 1.3 m 2 / g, optional range is 0.6~0.9m 2 / g, in the example, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g or a range between any two specific surface area values. The specific surface area in this range can improve the stability of the contact interface between the layered oxide and the electrolyte, thereby improving the electrochemical properties such as the cycle performance.
[0141] According to the test, the compaction density of the layered oxide represented by the chemical formula (I) in the above embodiments under a pressure of 2 tons is 2.8-3.1 g / cm 3 , optional: 2.9~3.09g / cm 3 In the example, the compaction density under 2 tons of pressure is 2.8g / cm 3 , 2.9g / cm 3 , 3g / cm 3 、3.09g / cm 3 、3.1g / cm 3 Typical but non-limiting compacted densities or ranges between any two compacted density values.
[0142] In the embodiments, the compacted density of the layered oxide represented by chemical formula (I) in the above embodiments under a pressure of 3 tons is 3.1 to 3.3 g / cm 3 , can be selected as 3.15~3.28g / cm 3 In the example, the compaction density under 3 tons of pressure is 3.1g / cm 3 、3.15g / cm 3 、3.2g / cm 3 , 3.25g / cm 3 、3.28g / cm 3 、3.3g / cm 3 Typical but non-limiting compacted densities or ranges between any two compacted density values.
[0143] The above compaction density range can improve the energy density and corresponding electrochemical performance of the battery containing the layered oxide represented by the above chemical formula (I).
[0144] Based on the morphology, crystal form, particle size and compacted density of the layered oxide shown in the chemical formula (I) in the above embodiments, in the embodiments, after testing, the layered oxide has a charge capacity of 164 to 174 mAh / g at 1.5 to 4.2 V and 0.1 C, which can be 165 to 172 mAh / g; the discharge capacity is 158 to 165 mAh / g, which can be 160 to 163 mAh / g. In other embodiments, the first efficiency of the layered oxide at 1.5 to 4.2 V and 0.1 C is 92 to 98%, which can be 92 to 95%.
[0145] The charge gram capacity and discharge gram capacity and first effect of the layered oxide refer to the gram capacity and first effect of the layered oxide, specifically, the layered oxide is prepared into a positive electrode for sodium ion buckle battery, and assembled with a negative electrode into a sodium ion buckle battery. The gram capacity and first effect are obtained by testing the sodium ion buckle battery. From the gram capacity and first effect range of the layered oxide, it can be seen that the structural stability of the layered oxide crystal has been significantly improved, the structural stability during the sodium insertion and extraction process, high gram capacity, and good cyclic stability of the reversible capacity.
[0146] In the embodiment, the sodium ion button cell used to test the charge gram capacity and discharge gram capacity of the layered oxide and the first effect is assembled as follows:
[0147] Positive electrode sheet: The layered oxide represented by the above chemical formula (I) is used as a positive electrode active material, and is fully stirred and mixed with a conductive agent carbon nanotube, a conductive agent carbon black, and a binder polyvinylidene fluoride (PVDF) in a weight ratio of 95:0.5:2:2.5 in an appropriate amount of solvent NMP to form a uniform positive electrode slurry; the positive electrode slurry is uniformly coated on the surface of a 13 μm positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained;
[0148] Negative electrode sheet: hard carbon, conductive agent SP, and CMC binder are added to deionized water in a weight ratio of 8:1:1 and stirred thoroughly to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of a 6μm copper foil, and after drying and cold pressing, a negative electrode sheet is obtained;
[0149] Electrolyte: 1M NaPF 6 / (EC / DEC, volume ratio 1:1);
[0150] Diaphragm: Glass fiber;
[0151] Sodium ion button cell assembly: stack the above positive electrode sheet, glass fiber film and negative electrode sheet in order to form a button cell assembly, put the electrode assembly into the packaging shell, add 1M NaPF 6 / (EC / DEC, volume ratio 1:1) electrolyte, after packaging, formation, standing and other processes, a sodium ion battery is obtained.
[0152] Based on the above embodiments, the positive electrode material of the present application embodiment may only contain the layered oxide shown in the chemical formula (I) in the above embodiments. Of course, it may further include other positive electrode materials, such as one or more of polyanion compounds, Prussian blue compounds, and other layered oxides.
[0153] In an exemplary embodiment, the polyanion compound may include at least one of sodium vanadium phosphate, sodium iron pyrophosphate, sodium iron phosphate, sodium fluoroferric phosphate, and the like.
[0154] In an exemplary embodiment, the Prussian blue compound may include Na 2 Fe[Fe(CN) 6 ](FeHCF), Na 2 Mn[Fe(CN) 6 ](MnHCF) etc.
[0155] The above-mentioned other positive electrode materials can, together with the layered oxide represented by the above chemical formula (I), further improve the electrochemical properties such as energy density, reversible capacity, and cycle performance of the battery containing the positive electrode material of the embodiment of the present application.
[0156] Preparation method of positive electrode material
[0157] In a second aspect, the present application provides a method for preparing the positive electrode material of the above-mentioned embodiment of the present application. In some embodiments, the method for preparing the positive electrode material of the embodiment of the present application includes the following steps:
[0158] S10: Provides Na q Ni x Mn y Fe z Zn p M i O j Precursor of
[0159] S20: Sintering the precursor to obtain a product having a chemical formula of Na q Ni x Mn y Fe z Zn p M i O j of layered oxides.
[0160] In step S10 of the method for preparing the positive electrode material in the embodiment of the present application, Na q Ni x Mn y Fe z Zn p M i Oj The precursor of is the precursor of the layered oxide shown in the chemical formula (I) contained in the positive electrode material of the above-mentioned application example. q Ni x Mn y Fe z Zn p M i O j The contained q, x, y, z, p, i and j are respectively in the following ranges:
[0161] 0.8≤q≤1; 0.1≤x≤0.3, optionally 0.15≤x≤0.25; 0.2≤y≤0.5, optionally 0.25≤y≤0.45; 0.2≤z≤0.35, optionally 0.25≤z≤0.32; 0.02≤p≤0.075, optionally 0.04≤p≤0.07, 0.04≤p≤0.065; 0≤i≤0.1, optionally 0≤i≤0.05; 1.8≤j≤2; and x+y+z+p+i≤1; M is an active or / and inert doping metal element, in the exemplary embodiment, the doping metal element includes at least one of V, Ca, Cr, Al, Sc, Sn, Sb, Zr, Nb, Ti, Mg, Cu, Ru, and Ir. The sintering treatment in step S20 is to make the Na in step S10 q Ni x Mn y Fe z Zn p M i O j The precursor is reacted to generate the layered oxide represented by the chemical formula (I) contained in the positive electrode material of the above application embodiment.
[0162] The positive electrode material preparation method of the present application embodiment is to q Ni x Mn y Fe z Zn p M i O j The precursor is sintered to generate the positive electrode material of the above application example having the chemical formula of Na q Ni x Mn y Fe z Zn p M i O jTherefore, the layered oxide prepared by the positive electrode material preparation method of the present application embodiment has a low zinc content and high structural stability during the sodium insertion and extraction process, so that the prepared layered oxide has a high gram capacity and a cyclic stability of its reversible capacity. At the same time, it also has high air stability and diffusion rate. In addition, for Na q Ni x Mn y Fe z Zn p M i O j The sintering conditions of the precursor can be effectively controlled, thereby improving the q Ni x Mn y Fe z Zn p M i O j The stability of the structure and electrochemical properties of layered oxides.
[0163] Step S10:
[0164] Na in step S10 q Ni x Mn y Fe z Zn p M i O j The precursor can be based on Na q Ni x Mn y Fe z Zn p M i O j The sodium source, nickel source, manganese source, iron source, zinc source and the doping element source shown in M are prepared by a solid phase method or a precipitation method according to the stoichiometric amount of the elements contained, such as moles or mass ratios converted according to moles.
[0165] When Na q Ni x Mn y Fe z Zn p M i O j When the precursor is Na q Ni x Mn y Fe z Zn p M i O j The precursor can be prepared according to a method comprising the following steps:
[0166] Step S11: According to Na q Ni x Mn y Fe z Zn p M i O j The sodium source, nickel source, manganese source, iron source, zinc source and the doping element source shown in M are solid-phase mixed to obtain Na q Ni x Mn y Fe z Zn p M i O j precursor.
[0167] In step S11, solid phase mixing treatment is relative to liquid phase mixing, which generally means that no solvent is added during the mixing process, such as no water is added. It is also the dry mixing treatment of the sodium source, nickel source, manganese source, iron source and zinc source or further containing the doping element source shown in M solid under solvent-free conditions.
[0168] In order to improve the uniformity of mixing of the sodium source, nickel source, manganese source, iron source and zinc source or further containing the doping element source shown in M during the solid phase mixing process, in the embodiment, the nickel source, manganese source, iron source and zinc source or further containing the doping element source shown in M can be mixed first, and then the sodium source is added for re-mixing. This improves the mixing uniformity of each source and improves the safety of the solid phase mixing process.
[0169] In the embodiment, the mixing treatment may be coated but not limited to ball milling treatment, as long as it can improve the uniformity of the mixing of the sodium source, nickel source, manganese source, iron source and zinc source or further contain the doping element source shown in M, it is within the scope disclosed in the embodiment of the present application. In the embodiment, when the mixing treatment is ball milling treatment, the speed of the ball mill can be controlled to be 300 to 1000 rpm, and can be optionally 400 to 600 rpm; the time of the ball milling treatment can be 1h to 6h, and can be optionally 2h to 4h. By ball milling treatment, the mixing uniformity of each source can be improved, so that the Na in step S20 can be finally improved. q Ni x Mn y Fe z Zn p M i O j The stability of the structure and electrochemical properties of layered oxides.
[0170] In an exemplary embodiment, the sodium source may be a sodium salt, such as at least one of sodium carbonate, sodium hydroxide, and the like.
[0171] In an exemplary embodiment, the nickel source may be a soluble or insoluble nickel compound, such as nickel oxide (NiO) or a nickel salt, etc. The nickel salt may include at least one of nickel nitrate, nickel carbonate, nickel hydroxide, nickel sulfate, etc.
[0172] In an exemplary embodiment, the manganese source may be a soluble or insoluble manganese compound, such as manganese oxide (Mn 2 O 3 ) or manganese salts, etc. Among them, the manganese salt may include at least one of manganese nitrate, manganese carbonate, manganese hydroxide, manganese sulfate, etc.
[0173] In an exemplary embodiment, the iron source may be a soluble or insoluble iron compound, such as an iron oxide (such as Fe 2 O 3 ) or iron salts, etc. Among them, the iron salt may include at least one of iron nitrate, iron carbonate, iron hydroxide, iron sulfate, etc.
[0174] In an exemplary embodiment, the zinc source may be a soluble or insoluble zinc compound, such as zinc oxide (such as ZnO) or a zinc salt, etc. The zinc salt may include at least one of zinc nitrate, zinc carbonate, zinc hydroxide, zinc sulfate, etc.
[0175] In the exemplary embodiment, the doping metal element source shown in M may be a soluble or insoluble compound of the doping metal element shown in M, such as an oxide of the doping metal element shown in M or a salt of the doping metal element shown in M. The salt of the doping metal element shown in M may include at least one of nitrates, carbonates, hydroxides, sulfates, etc. of the doping metal element shown in M.
[0176] The above-mentioned sodium source, nickel source, manganese source, iron source and zinc source or further containing the doping element source represented by M can be effectively mixed uniformly during the mixing process to increase the Na q Ni x Mn y Fe z Zn p M i O j The precursor to generate Na q Ni x Mn y Fe z Zn p M i O j Structural and chemical stability of layered oxides.
[0177] When Na is prepared by precipitation method q Ni x Mn y Fe z Zn p M i Oj When the precursor is Na q Ni x Mn y Fe z Zn p M i O j The precursor can be prepared according to a method comprising the following steps:
[0178] Step S12: According to Na q Ni x Mn y Fe z Zn p M i O j A soluble nickel source, a soluble manganese source, a soluble iron source, a soluble zinc source or a soluble doping element source represented by M is prepared into a mixed solution according to the stoichiometric ratio of the elements, and at least one of a precipitant and a complexing agent is added to perform a coprecipitation treatment to obtain a precipitated mixture;
[0179] Step S13: Mixing the precipitated mixture with a sodium source to obtain Na q Ni x Mn y Fe z Zn p M i O j precursor.
[0180] In step S12, at least one of the precipitant and the complexing agent should be a compound that can precipitate nickel, manganese, iron, zinc and the doping metal element shown in M in the nickel source, soluble manganese source, soluble iron source, soluble zinc source and the soluble doping element source shown in M. For example, in the embodiment, the precipitant may include at least one of alkali metal hydroxides, carbonates, etc.
[0181] In an embodiment, the complexing agent may include an inorganic or organic complexing agent. In a demonstration example, the inorganic complexing agent may include at least one of ammonia water, ammonium bicarbonate, ammonium sulfate, ammonium carbonate, etc.; the organic complexing agent may include at least one of citric acid, tartaric acid and disodium ethylenediaminetetraacetic acid (EDTA), aminotriacetic acid (NTA), etc.
[0182] These types of precipitants and complexing agents can effectively precipitate nickel, manganese, iron, zinc and the doping elements shown in M.
[0183] In the embodiment, at least one of the precipitant and the complexing agent should be in excess relative to the total amount of metal elements contained in the mixed solution, such as the total molar amount, to ensure that all metal elements contained in the mixed solution are fully precipitated to increase the Na q Nix Mn y Fe z Zn p M i O j The accuracy of the stoichiometric ratio of the metal elements contained in the precursor.
[0184] In an exemplary embodiment, the soluble nickel source may include at least one of nickel acetate, nickel chloride, nickel nitrate, and nickel sulfate.
[0185] In an exemplary embodiment, the soluble manganese source may include at least one of manganese nitrate, manganese sulfate, and manganese halide.
[0186] In an exemplary embodiment, the soluble iron source may include at least one of iron nitrate, manganese sulfate, and halides.
[0187] In an exemplary embodiment, the soluble zinc source may include at least one of zinc nitrate, manganese sulfate, and halides.
[0188] In an exemplary embodiment, the soluble doping metal element source M may include at least one of nitrates, manganese sulfate, halides, etc. of the doping metal element M.
[0189] The above-mentioned soluble nickel source, soluble manganese source, soluble iron source, soluble zinc source and soluble doping element source represented by M all have good solubility and can quantitatively control the stoichiometric ratio of each metal element in the precipitation mixture.
[0190] The mixing ratio between the sodium source and the precipitation mixture in step S13 should satisfy Na q Ni x Mn y Fe z Zn p M i O j The mixing process can be a solid phase mixing process or a process in which a soluble sodium source is dissolved and mixed with the precipitation mixture, and then the solvent is removed.
[0191] In an exemplary embodiment, the sodium source may be a sodium salt, such as at least one of sodium carbonate, sodium hydroxide, and the like.
[0192] In addition, there is no sequential relationship between the above step S11, step S12 and step S13.
[0193] Step S20:
[0194] In step S20, Na in step S10 q Ni x Mn y Fe z Znp M i O j After the precursor is sintered, a chemical formula of Na q Ni x Mn y Fe z Zn p M i O j The study found that the sintering conditions have a great influence on the formation of Na q Ni x Mn y Fe z Zn p M i O j The structural stability and electrochemical properties of the layered oxide are affected to a certain extent. In some embodiments, the sintering temperature can be controlled at 700-980°C, optionally 750-950°C, and in exemplary embodiments, it can be 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 980°C, and other typical but non-limiting temperatures or a range between any two temperature values.
[0195] At the above sintering temperature, the sintering time can be 4h to 20h, and can be 6h to 12h. In the exemplary embodiment, it can be 4h, 5h, 8h, 10h, 12h, 15h, 18h, 20h and other typical but non-limiting hours or any range between two hours.
[0196] By controlling the stability and time of the sintering process within the above range, the Na in step S10 can be q Ni x Mn y Fe z Zn p M i O j The precursor reacts to generate Na q Ni x Mn y Fe z Zn p M i O j layered oxides, and can further increase the Na q Ni x Mn y Fe z Zn p M i O j The structural stability of the layered oxide during the sodium insertion and extraction process further improves the high specific capacity of the layered oxide and the cycle stability of its reversible capacity. q Nix Mn y Fe z Zn p M i O j The content of O3 phase layered metal oxide and the single crystal content in the layered oxide control the single crystal size and the particle size of the layered oxide, thereby increasing the compaction density of the layered oxide.
[0197] In an embodiment, the temperature of the sintering process can be increased to the temperature of the sintering process at a heating rate of 2 to 15°C / min. The heating rate can be further controlled to be 4 to 10°C / min. In a demonstration example, the heating rate can be a typical but non-limiting rate such as 2°C / min, 4°C / min, 6°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min, 17°C / min, 18°C / min, 20°C / min, or a range between any two rate values. By controlling the heating rate of the sintering process, such as controlling it in this heating rate range, the Na q Ni x Mn y Fe z Zn p M i O j The crystals of the layered oxide are perfect and complete, such as improving the uniformity of the crystal morphology.
[0198] In addition, the sintering process in the above step S20 should be understood to be carried out in an aerobic environment. For example, in the embodiment, the sintering process can be carried out in air or in an oxygen-containing protective atmosphere, such as oxygen-containing nitrogen or other inert atmospheres.
[0199] positive electrode
[0200] In a third aspect, the embodiments of the present application provide a positive electrode. In some embodiments, the positive electrode of the embodiments of the present application includes a current collector and a positive electrode active material layer. The positive electrode active material layer is combined with the current collector, and the positive electrode active material layer contains the positive electrode material of the embodiments of the present application.
[0201] In the positive electrode of the embodiment of the present application, the current collector refers to a structure for collecting current and for transmitting electrons. The positive electrode active material layer refers to a layer structure containing a positive electrode active material, which is a key substance participating in the battery chemical reaction in the positive electrode. Among them, the positive electrode active material includes the positive electrode material of the embodiment of the present application. The positive electrode active material layer is combined with the current collector, which means that the positive electrode active material layer is at least combined with the surface of the current collector. In addition, the positive electrode can be a pole piece, which means that the positive electrode has a sheet-like morphology. Of course, it can also be set to other morphologies as needed.
[0202] Since the positive electrode active material layer of the positive electrode of the embodiment of the present application contains the positive electrode material of the embodiment of the present application, the positive electrode has a relatively high gram capacity and good cycle performance.
[0203] In the embodiment, the current collector contained in the positive electrode of the embodiment of the present application includes but is not limited to a metal current collector, a carbon current collector, a conductive resin current collector, a composite current collector of metal and resin, etc., more specifically, aluminum, copper, nickel, titanium, iron and their respective alloys, stainless steel, carbon fiber, carbon nanotubes (CNT), graphite, etc. In the embodiment, the current collector can also be a dense film layer or a film layer with a porous structure. In the embodiment, the current collector can be but is not limited to aluminum foil or porous aluminum foil, etc.
[0204] In the embodiment, the positive electrode active material layer contained in the positive electrode of the embodiment of the present application is combined with the current collector and can be at least stacked on the surface of the current collector. When the surface layer of the current collector contains a porous structure or the current collector itself is a porous structure, the positive electrode active material layer can be at least partially embedded in the current collector.
[0205] In some embodiments, the positive electrode active material layer is at least bonded to the surface of the current collector and can be as follows: Figure 3 In the structure shown, the positive electrode active material layer 12 is stacked on one surface of the current collector 11. When the surface of the current collector 11 has a porous structure or the current collector 11 is a porous structure as a whole, the positive electrode active material layer 12 can be further extended into the porous structure of the current collector 11 in addition to being stacked and bonded on the surface of the current collector 11.
[0206] In other embodiments, the positive electrode active material layer is at least bonded to the surface of the current collector and can be as follows: Figure 4 In the structure shown, the current collector 11 has two surfaces arranged opposite to each other, and the positive electrode active material layer 12 is stacked on the two surfaces arranged opposite to each other of the current collector 11. When at least one of the two surfaces of the current collector 11 has a porous structure or the current collector 11 is a porous structure as a whole, the positive electrode active material layer 12 can be further extended into the porous structure of the current collector 11 in addition to being stacked and bonded on the two surfaces of the current collector 11.
[0207] As an embodiment of the present application, in the above-mentioned positive electrode active material layer, the mass content of the layered oxide shown in the chemical formula (I) contained in the positive electrode material of the above-mentioned text application embodiment in the positive electrode active material layer can be 90% to 98%, optionally 92% to 96%. In the exemplary embodiment, it can be 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% and other typical but non-limiting contents or the range between any two content values. The layered oxide in this content range can effectively increase the gram capacity of the positive electrode and thus increase the energy density of the battery, and has good cyclability. Since the layered oxide also has good processing properties, it also effectively improves the film quality of the positive electrode active material layer.
[0208] In addition to the above-mentioned positive electrode active material components, the positive electrode active material layer contained in the positive electrode of each application embodiment generally includes components such as a binder and a conductive agent. The binder can enhance the mechanical properties between the positive electrode active material layer itself and the current collector. The conductive agent can effectively improve the conductivity of the positive electrode, such as reducing the resistance of the positive electrode.
[0209] In an embodiment, the mass content of the binder contained in the above-mentioned positive electrode active material layer can be 0.5% to 5%, optionally 1% to 3%. In a demonstration example, it can be 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, 3% and other typical but non-limiting contents or a range between any two content values.
[0210] In an embodiment, the binder may include one or more of an oil-soluble binder, a water-soluble binder, an emulsion-type binder, etc. In an exemplary example, the oil-soluble binder may include one or more of polyvinylidene fluoride, polyimide, polytetrafluoroethylene, polybutyl acrylate, polyacrylonitrile, etc.; in an exemplary example, the water-soluble binder may include one or more of carboxymethyl cellulose, carboxymethyl cellulose salt, polyacrylic acid, polyacrylic acid salt, polyvinyl alcohol, sodium alginate, cyclodextrin, etc.; in an exemplary example, the emulsion-type binder may include one or more of styrene-butadiene rubber, vinyl acetate resin, acrylic resin, and chlorinated rubber.
[0211] The content within this range and the above-mentioned types of binders can effectively enhance the mechanical properties of the positive electrode active material layer and the bonding strength between the positive electrode and the current collector, and can effectively improve the cycle performance of the positive electrode.
[0212] In an embodiment, the mass content of the conductive agent contained in the above-mentioned positive electrode active material layer can be 0.5% to 5%, optionally 1% to 3%. In a demonstration example, it can be 0.5%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.8%, 3% and other typical but non-limiting contents or a range between any two content values.
[0213] In an embodiment, the conductive agent may include at least one of a granular conductive agent, a linear conductive agent, etc. The granular conductive agent may include one or more of acetylene black (SP), conductive carbon black (super-P), Ketjen black, graphene, etc. The linear conductive agent may include one or more of carbon nanotubes, carbon fibers, conductive oxide nanowires, etc. The granular conductive agent is a conductive agent with a nonlinear particle morphology relative to a linear conductive agent. A linear conductive agent refers to a conductive agent with a one-dimensional fiber morphology.
[0214] The content within this range and the above-mentioned types of conductive agents can effectively improve the conductivity of the positive electrode active material layer.
[0215] In the embodiments, the conductive agent contained in the positive electrode active material layer in the positive electrode of each embodiment above includes a linear conductive agent and a granular conductive agent. The mass content of the linear conductive agent in the positive electrode active material layer is 0.1% to 2.5%, and can be 0.2% to 0.8%. In the exemplary embodiment, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, etc., which are typical but non-limiting contents or the range between any two content values. Since the crystals of the layered oxide shown in the chemical formula (I) contained in the positive electrode material of the above text application embodiment include single crystals, and the morphology of the single crystal is flat, a linear conductive agent is added to the positive electrode active material layer, and the content of the linear conductive agent is controlled within this range, so that the linear conductive agent can form a rich conductive network structure in the positive electrode active material layer, and the linear conductive agent can also be entangled on the surface of the flat single crystal particles. The granular conductive agent can be effectively dispersed in the gaps of the positive electrode material. In this way, the linear conductive agent constructs a long-range conductive network structure in the positive electrode active material layer, and the granular conductive agent constitutes a short-range conductive structure. Therefore, the conductive synergistic effect of the linear conductive agent and the granular conductive agent in the positive electrode active material layer effectively improves the conductivity of the positive electrode active material layer, and can significantly reduce the internal resistance of the positive electrode.
[0216] In the embodiment, the aspect ratio of the linear conductive agent can be controlled to be 40 to 3000:1, and can be 50 to 2500:1. In the exemplary embodiment, the aspect ratio can be 40:1, 50:1, 100:1, 500:1, 1000:1, 1500:1, 2000:1, 2500:1, 3000:1, etc., which are typical but non-limiting aspect ratios, or a range between any two aspect ratios. The aspect ratio refers to the ratio of the length to the diameter of the linear conductive agent.
[0217] In a further embodiment, the length of the linear conductive agent can be selected to be 0.5 to 5 μm, or optionally 0.5 to 2 μm. In the exemplary embodiment, it can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc. typical but non-limiting lengths or a range between any two length values.
[0218] In a further embodiment, the diameter of the linear conductive agent can be selected to be 2 to 10 nm, or optionally 3 to 7 nm. In the exemplary embodiment, the diameter can be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, etc., which are typical but non-limiting diameters, or a range between any two diameter values.
[0219] By controlling the aspect ratio of the linear conductive agent within the above range, or further controlling the length and diameter of the linear conductive agent within the above range, the linear conductive agent can construct a richer long-range conductive network structure in the positive electrode active material layer, further enhancing the conductive synergistic effect of the linear conductive agent and the particulate conductive agent, so as to further improve the conductivity of the positive electrode active material layer.
[0220] In the embodiments, the positive electrode active material layer in the positive electrode of each embodiment above may contain other additives in addition to the positive electrode active material, binder and conductive agent. In the embodiments, the additives may include but are not limited to functional components such as sodium supplement additives.
[0221] In some embodiments, the content of the positive electrode active material layer on a single surface of the current collector in the above embodiments, that is, the coating weight (CW) is 260-350 mg / 1540.25 mm 2 , optional: 280~320mg / 1540.25mm 2 In the example, it can be 260mg / 1540.25mm 2 、270mg / 1540.25mm 2 、280mg / 1540.25mm 2 、290mg / 1540.25mm 2 、300mg / 1540.25mm 2 、310mg / 1540.25mm 2 、320mg / 1540.25mm 2 、330mg / 1540.25mm 2 、340mg / 1540.25mm 2 、350mg / 1540.25mm 2Typical but non-limiting contents or ranges between any two content values. The coating weight refers to the weight of the positive electrode active material layer per unit area. The coating weight in this range can effectively increase the gram capacity of the positive electrode and thus increase the energy density of the battery.
[0222] In some embodiments, the compaction density of the positive electrode active material layer in the above embodiments may be 2.8 to 3.4 g / cm 3 , can be selected as 2.9~3.2g / cm 3 In the example, it can be 2.8 g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm 3 Typical but non-limiting compaction densities or ranges between any two compaction density values. The compaction density refers to the weight of the positive electrode active material layer per unit volume. The compaction density in this range can effectively increase the gram capacity of the positive electrode and thus increase the energy density of the battery, and has good interface stability with the electrolyte.
[0223] In some embodiments, the porosity of the positive electrode active material layer in the above embodiments may be 40% to 65%, and may be 45% to 60%. In the exemplary embodiment, it may be 40%, 43%, 45%, 48%, 50%, 53%, 55%, 58%, 60%, 63%, 65%, or other typical but non-limiting porosities or a range between any two porosity values. The porosity refers to the total volume of pores contained in the unit volume of the positive electrode active material layer and the percentage of the unit volume of the positive electrode active material layer. The porosity in this range enables the positive electrode active material layer to have the above-mentioned compaction density, thereby increasing the gram capacity of the positive electrode and thus increasing the energy density of the battery, and also increasing the wettability of the electrolyte.
[0224] In some embodiments, the positive electrode in each of the above embodiments is a pole piece, and the membrane resistance of the positive electrode active material layer in each of the above embodiments can be 0.5 to 5 mΩ, and can be optionally 0.5 to 3 mΩ. In the exemplary embodiment, it can be a typical but non-limiting membrane resistance of 0.5 mΩ, 1 mΩ, 1.5 mΩ, 2 mΩ, 2.5 mΩ, 3 mΩ, 3.5 mΩ, 4 mΩ, 4.5 mΩ, 5 mΩ, etc., or a range between any two membrane resistance values. The pole piece has a sheet-like morphology as described above, and therefore, it has two opposite surfaces. The membrane resistance refers to the resistance value between one surface of the sheet-like positive electrode to the other opposite surface. The membrane resistance in this range can effectively improve the performance of the battery including efficiency and life.
[0225] In some embodiments, the positive electrode is a pole piece in each of the above embodiments, and the ratio of the thickness from one surface of the pole piece to the other opposite surface to the thickness of the current collector is 6 to 15:1, and can be 8 to 14:1. In the exemplary examples, it can be 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1 and other typical but non-limiting ratios or the range between any two ratios. The thickness refers to the vertical distance from one surface of the layer structure to the other opposite surface. When Figure 3 When a positive electrode active material layer is disposed on one surface of the current collector shown in FIG. 1 , the thickness from one surface of the pole piece to the other opposite surface refers to the sum of the thickness of a positive electrode active material layer and the thickness of the current collector; when Figure 4 When both surfaces of the current collector shown contain positive electrode active material layers, the thickness from one surface of the pole piece to the other opposite surface refers to the sum of the thicknesses of the two positive electrode active material layers plus the sum of the thicknesses of the current collector.
[0226] In the embodiment, the thickness of the positive electrode active material layer contained in the pole piece can be controlled to be 104-182 μm, and further can be 110-170 μm. In the exemplary embodiment, it can be 104 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 182 μm, etc., which are typical but non-limiting thicknesses, or a range between any two thickness values. In the embodiment, the thickness of the current collector can be, but is not limited to, 13 μm.
[0227] By controlling the total thickness of the pole piece and the thickness of the current collector within the above-mentioned ratio range or specific thickness range, the gram capacity of the pole piece can be effectively increased, thereby increasing the energy density of the battery, and increasing the bonding strength between the positive electrode active material layer and the current collector, thereby increasing the mechanical strength of the pole piece structure and improving the cycle performance of the pole piece.
[0228] Preparation method of positive electrode:
[0229] The present application also provides a method for preparing the positive electrode of the above embodiment. In some embodiments, the method for preparing the positive electrode of the above embodiment comprises the following steps:
[0230] S30: mixing components including positive electrode active material, binder, conductive agent and the like in a solvent in proportion to prepare positive electrode slurry;
[0231] S40: The positive electrode slurry is subjected to a film-forming treatment on the current collector to form a positive electrode active material layer, thereby obtaining a positive electrode.
[0232] Step S30:
[0233] The positive electrode active material in step S30 includes the positive electrode material of the above-mentioned embodiment of the present application, and specifically includes the layered oxide represented by the above-mentioned chemical formula (I).
[0234] The positive electrode active material, binder, conductive agent and other components in step S30 can be mixed according to the content ratio of the corresponding components contained in the positive electrode active material layer of the positive electrode. The solvent can be an organic solvent or water suitable for preparing positive electrode slurry.
[0235] The mixing process in step S30 can be carried out according to the conventional electrode slurry preparation method, such as but not limited to stirring, until the components are evenly dispersed to form a stable positive electrode slurry. Of course, the viscosity and other properties of the positive electrode slurry should meet the requirements of the film forming process so as to form a positive electrode active material layer that meets the quality requirements on the current collector.
[0236] Step S40:
[0237] Based on the positive electrode slurry components prepared in step S30, the positive electrode active material layer prepared in step S40 is the positive electrode active material layer contained in the positive electrode of the above embodiment of the present application.
[0238] In step S40, the positive electrode slurry may be film-formed on the current collector in accordance with a conventional positive electrode active material layer method. For example, in the embodiment, the electrode slurry may be first formed into a wet film on the current collector; then a drying process is performed to volatilize the solvent, thereby drying the wet film; and then the dried film layer is roll-pressed to form a positive electrode active material layer, thereby obtaining a positive electrode.
[0239] Of course, the positive electrode active material layer can also be prepared by improving the conventional positive electrode active material layer preparation method, or by adopting a new method. As long as the electrode slurry in step S30 is used to prepare the positive electrode active material layer on the current collector, it is within the scope disclosed in the embodiment of the present application.
[0240] In addition, the film forming treatment conditions in S40 can be controlled and adjusted, such as the conditions for forming a wet film on the current collector of the positive electrode slurry configured in step S30, the conditions for the roller pressing treatment, etc., and the related properties of the formed positive electrode active material layer can be controlled and adjusted, such as controlling and adjusting the content of the positive electrode active material layer on the single side of the current collector to 260-350 mg / 1540.25 mm as above. 2 Range, compaction density control and adjustment to 2.8 ~ 3.4g / cm as above 3 range, the porosity is controlled and adjusted to the range of 40% to 65% as mentioned above, the diaphragm resistance of the electrode is controlled and adjusted to the range of 0.5 to 5 mΩ as mentioned above, etc.
[0241] Battery
[0242] In a fourth aspect, an embodiment of the present application also provides a sodium battery.
[0243] In the embodiment, the sodium battery of the embodiment of the present application may include any one of a sodium battery cell, a battery module, and a battery pack.
[0244] Sodium battery cells:
[0245] A sodium battery cell is also called a sodium battery core, which includes a battery outer package and an electrode assembly encapsulated in the battery outer package. The number of electrode assemblies contained in a battery cell can be one or more, which can be adjusted according to actual needs.
[0246] The outer packaging of the sodium battery cell can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc.; it can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate. The shape of the outer packaging can be cylindrical, square, or any other shape. The shape of the outer packaging gives the shape of the sodium battery cell, so the shape of the sodium battery cell can also be cylindrical, square, or any other shape corresponding to the shape of the outer packaging. In the exemplary embodiment, the sodium battery cell can be as follows: Figure 5 The battery cell 20 shown has a square structure.
[0247] In some embodiments, Figure 6 As shown, the outer packaging of the battery cell 20 may include a shell 21 and a cover plate 23. The shell 21 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 21 has an opening connected to the receiving cavity, and the cover plate 23 is used to cover the opening to close the receiving cavity. One or more electrode assemblies 22 are encapsulated in the receiving cavity.
[0248] In the embodiment, the sodium battery cell may be a sodium battery cell containing an electrolyte, or a sodium battery cell containing a solid electrolyte.
[0249] When it is a sodium battery cell containing an electrolyte, the electrode assembly contained in the sodium battery cell generally includes a positive electrode, a negative electrode and a separator. The positive electrode and the negative electrode are alternately stacked, and the separator is stacked between the positive electrode and the negative electrode to play an isolation role, separating the positive electrode from the negative electrode. The positive electrode, the separator layer and the negative electrode can form an electrode assembly of a laminated structure through a lamination process, or can form an electrode assembly of a core structure through a winding process. The electrode assembly containing the separator is placed in an outer package, the electrolyte is injected and the electrode assembly is soaked, and the sodium battery cell is obtained by packaging.
[0250] When it is a sodium battery cell containing a solid electrolyte, the electrode assembly contained in the sodium battery cell generally includes a positive electrode, a negative electrode and a solid electrolyte. The positive electrode and the negative electrode are alternately stacked, and the solid electrolyte is stacked between the positive electrode and the negative electrode to play an isolating role, separating the positive electrode from the negative electrode. The electrode assembly containing the solid electrolyte is placed in an outer package, and the sodium battery cell is obtained by packaging.
[0251] In each of the above-mentioned sodium battery monomers, the positive electrode contained in the electrode assembly is the positive electrode of the above-mentioned application embodiment, that is, its positive electrode active material layer contains the positive electrode material of the above-mentioned application embodiment, specifically, contains the layered oxide represented by the above-mentioned chemical formula (I).
[0252] In this way, the sodium battery cell has high energy density and good cycle performance.
[0253] As shown in the embodiment, the energy density of the sodium battery monomer can reach 110-160Wh / kg, and can be 120-155Wh / kg. The 1000 cycle capacity retention rate under 0.5C / 1C charging and discharging conditions in the range of 1.5-4.05V can reach 70-95%, and can be 80-90%.
[0254] In each of the above-mentioned sodium battery cells, the negative electrode contained in the electrode assembly includes a negative electrode current collector, and optionally includes a negative electrode active material layer disposed on the surface of the negative electrode current collector, and the negative electrode active material layer contains a negative electrode active material. In an embodiment, the negative electrode current collector may include, but is not limited to, a metal or a composite current collector. For example, as a metal, sodium, sodium alloy, copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc. may be used. In the case of using sodium or sodium alloy as the negative electrode current collector, since sodium or sodium alloy itself can also be used as a negative electrode active material, the negative electrode plate may not contain a negative electrode active material layer, and sodium or sodium alloy is both a current collector and a negative electrode active material.
[0255] The composite current collector may include a composite material of a polymer material and a metal, wherein the polymer material may include but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc., and the metal may include but is not limited to sodium, copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy. The composite current collector may be obtained by mixing a polymer material and a metal, or may be coated on at least one side of the polymer material by electroplating, coating or other methods.
[0256] When the negative electrode includes a negative electrode active material layer, the negative electrode active material in the negative electrode active material layer may include but is not limited to a mixture or composite material formed by any one or more of carbon-based materials, alloy materials, titanium-based materials, and sodium metal. The carbon-based materials include but are not limited to one or more of graphite, soft carbon, hard carbon, carbon microspheres, and carbon fibers; the alloy materials include but are not limited to one or more of sodium-tin alloys, sodium-germanium alloys, and sodium-antimony alloys; and the titanium-based materials include but are not limited to one or more of titanium dioxide, titanates, and titanium phosphates.
[0257] The mass content of the negative electrode active material in the negative electrode active material layer can be 85% to 98%, and can be optionally 95% to 98%. In the exemplary embodiment, it can be 85%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98% and other typical but non-limiting contents or the range between any two content values.
[0258] The negative electrode active material layer may also include at least one of a conductive agent and a binder. The conductive agent is used to collect current between the negative electrode active materials and between the active materials and the current collector to improve the electronic conductivity. At the same time, the conductive agent can also promote the infiltration of the electrolyte into the negative electrode sheet. The binder can improve the bonding strength between the various substances in the negative electrode active material layer and between the active layer and the current collector.
[0259] In the embodiment, the mass content of the conductive agent in the negative electrode active material layer can be 0.5% to 10%. In the exemplary embodiment, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and other typical but non-limiting contents or a range between any two content values, and can also be set to other contents as needed. In the exemplary embodiment, the conductive agent includes one or more of acetylene black (SP), carbon nanotubes, conductive carbon black (super-P), Ketjen black, carbon fiber, and graphene.
[0260] In the embodiment, the mass content of the binder in the negative electrode active material layer can be 0.5% to 10%. In the exemplary embodiment, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% and other typical but non-limiting contents or a range between any two content values, and can also be set to other contents as needed. In the exemplary embodiment, the binder includes but is not limited to polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, polyimide, polytetrafluoroethylene, polybutyl acrylate, polyacrylonitrile, carboxymethyl cellulose, carboxymethyl cellulose salt, polyacrylic acid, polyacrylate, polyvinyl alcohol, sodium alginate, cyclodextrin, styrene-butadiene rubber, vinyl acetate resin, acrylic resin, chlorinated rubber and one or more thereof.
[0261] In the embodiment, the negative electrode active material layer may also optionally include a thickener, such as but not limited to carboxymethyl cellulose (CMC). The mass content of the thickener in the negative electrode active layer may be set to 0.5% to 5%. In the exemplary embodiment, it may be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., which are typical but non-limiting contents, or a range between any two content values.
[0262] In the embodiment, when each of the sodium battery cells mentioned above contains a separator, the separator is arranged between the positive electrode and the negative electrode as described above to separate the positive electrode and the negative electrode. The separator can prevent electrons in the battery from passing freely to prevent contact short circuit between the electrodes, but can allow sodium ions in the electrolyte to pass freely between the positive electrode and the negative electrode. The separator can be any known porous structure separator with electrochemical stability and mechanical stability. In the exemplary embodiment, the separator includes a single layer or multilayer film of at least one of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP) and polyvinylidene fluoride (PVDF).
[0263] In the embodiment, when each of the above sodium battery monomers contains a solid electrolyte, the solid electrolyte is arranged between the positive electrode and the negative electrode as described above to separate the positive electrode and the negative electrode. The solid electrolyte may include at least one of a polymer solid electrolyte, an oxide electrolyte, a sulfide electrolyte, a borohydride electrolyte, a composite solid electrolyte, and the like.
[0264] Battery Module:
[0265] When the sodium battery in the embodiment of the present application is a battery module, the battery module refers to being assembled from the above-mentioned sodium battery monomers, that is, it can contain a plurality of the above-mentioned sodium battery monomers, and the specific number can be adjusted according to the application and capacity of the battery module.
[0266] In some embodiments, Figure 7 FIG. 3 is a schematic diagram of a battery module 30 as an example. Figure 7 As shown, in the battery module 30, a plurality of sodium battery cells 20 may be arranged in sequence along the length direction of the battery module 30. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 20 may be fixed by fasteners.
[0267] Optionally, the battery module 30 may further include a housing having an accommodation space in which the plurality of sodium battery cells 20 are accommodated.
[0268] Battery Pack:
[0269] When the sodium battery in the embodiment of the present application is a battery pack, the battery pack refers to the assembly of the above sodium battery monomers, that is, it can contain multiple sodium battery monomers, and the multiple sodium battery monomers are assembled into the above battery module. The specific number of battery monomers or battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0270] In some embodiments, Figure 8 and Fig. 94 is a schematic diagram of an exemplary battery pack 40. The battery pack 40 may include a battery box and a plurality of battery modules 30 disposed in the battery box. The battery box includes an upper box body 41 and a lower box body 42, wherein the upper box body 41 is used to cover the lower box body 42 and form a closed space for accommodating the battery modules 30. The plurality of battery modules 30 may be arranged in the battery box in any manner.
[0271] Electrical devices
[0272] In the fifth aspect, the embodiments of the present application also provide an electric device. The electric device of the embodiments of the present application includes a power supply unit or an energy storage unit, and of course may also include other auxiliary components or necessary components. Among them, the power supply unit or energy storage unit contains the sodium battery of the above-mentioned embodiments of the present application. For example, it can be the above-mentioned sodium battery cell, battery module or battery pack. Since the electric device of the embodiments of the present application contains the sodium battery of the above-mentioned embodiments of the present application, the power supply unit or energy storage unit of the electric device of the embodiments of the present application has high energy density, good cycle performance, long service life, and the electric device of the embodiments of the present application has a long standby or battery life.
[0273] In the embodiment, the electric device may include but is not limited to a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, for example, a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc. As the electric device, a battery cell, a battery module, or a battery pack in the battery may be selected according to its use requirements.
[0274] Fig.10 Schematic diagram of an electric device as an example. The electric device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device for high power and high energy density, a battery pack or a battery module can be used.
[0275] In the embodiment, when the electrical device contains an energy storage unit, the electrical device can be an energy storage device, and the energy storage device includes the energy storage unit, and of course can also include other auxiliary components or necessary components. Among them, the energy storage unit contains the battery of the above text application embodiment. The battery contained in the energy storage unit can be one or more. When there are multiple batteries, multiple batteries can form a battery module or battery pack. Since the energy storage device of the embodiment of the present application contains the battery of the above text application embodiment, the energy storage device has high energy density, good cycle performance, long service life, and further high energy density.
[0276] Example
[0277] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0278] 1. Examples of positive electrode materials and preparation methods thereof
[0279] Example A1
[0280] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.89 Ni 0.23 Mn 0.45 Fe 0.3 Zn 0.02 O 2 of layered oxides.
[0281] The positive electrode material preparation method comprises the following steps:
[0282] S1: According to Na 0.89 Ni 0.23 Mn 0.45 Fe 0.3 Zn 0.02 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and then excessive sodium carbonate was added in proportion for mixing to obtain a precursor;
[0283] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.89 Ni 0.23 Mn 0.45 Fe 0.3 Zn 0.02 O 2 layered oxide; wherein the sintering conditions are: temperature: 850°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0284] Example A2
[0285] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.89 Ni 0.23 Mn 0.44 Fe 0.3 Zn 0.03 O 2of layered oxides.
[0286] The positive electrode material preparation method comprises the following steps:
[0287] S1: According to Na 0.89 Ni 0.23 Mn 0.44 Fe 0.3 Zn 0.03 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0288] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.89 Ni 0.23 Mn 0.44 Fe 0.3 Zn 0.03 O 2 layered oxide; wherein the sintering conditions are: temperature: 860°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0289] Example A3
[0290] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Cu 0.02 O 2 of layered oxides.
[0291] The positive electrode material preparation method comprises the following steps:
[0292] S1: According to Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Cu 0.02 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3 , CuO are ball-milled at 500 rpm for 6 hours, and sodium carbonate is added in proportion for mixing to obtain a precursor;
[0293] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Cu 0.02 O 2 layered oxide; wherein the sintering conditions are: temperature: 865°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0294] Example A4
[0295] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.89 Ni 0.23 Mn 0.42 Fe 0.3 Zn 0.05 O 2 of layered oxides.
[0296] The positive electrode material preparation method comprises the following steps:
[0297] S1: According to Na 0.89 Ni 0.23 Mn 0.42 Fe 0.3 Zn 0.05 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0298] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.89 Ni 0.23 Mn 0.42 Fe 0.3 Zn 0.05 O 2 layered oxide; wherein the sintering conditions are: temperature: 865°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0299] Example A5
[0300] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.89 Ni 0.23 Mn 0.41 Fe 0.3 Zn 0.06 O2 of layered oxides.
[0301] The positive electrode material preparation method comprises the following steps:
[0302] S1: According to Na 0.89 Ni 0.23 Mn 0.41 Fe 0.3 Zn 0.06 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0303] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.89 Ni 0.23 Mn 0.41 Fe 0.3 Zn 0.06 O 2 layered oxide; wherein the sintering conditions are: temperature: 865°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0304] Example A6
[0305] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.89 Ni 0.23 Mn 0.42 Fe 0.285 Zn 0.065 O 2 of layered oxides.
[0306] The positive electrode material preparation method comprises the following steps:
[0307] S1: According to Na 0.89 Ni 0.23 Mn 0.42 Fe 0.285 Zn 0.065 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0308] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.89 Ni 0.23 Mn 0.42 Fe 0.285 Zn 0.065 O 2 layered oxide; wherein the sintering conditions are: temperature: 865°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0309] Example A7
[0310] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.89 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.07 O 2 of layered oxides.
[0311] The positive electrode material preparation method comprises the following steps:
[0312] S1: According to Na 0.89 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.07 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0313] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.89 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.07 O 2 layered oxide; wherein the sintering conditions are: temperature: 880°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0314] Example A8
[0315] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zn 0.075 O 2of layered oxides.
[0316] The positive electrode material preparation method comprises the following steps:
[0317] S1: According to Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zn 0.075 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0318] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zn 0.075 O 2 layered oxide; wherein the sintering conditions are: temperature: 880°C; time: 10h; heating rate: 5°C / min; oxygen atmosphere.
[0319] Embodiment A9
[0320] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zn 0.075 O 2 of layered oxides.
[0321] The positive electrode material preparation method comprises the following steps:
[0322] S1: According to Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zn 0.075 O 2 The molar ratio of the metal elements contained is such that nickel nitrate, zinc nitrate, manganese nitrate and iron nitrate are fully dissolved to prepare a mixed solution; a sufficient amount of ammonium carbonate is then added to the mixed solution for co-precipitation treatment to obtain a precipitated mixture;
[0323] S2: According to Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zn 0.075O 2 The sodium molar content ratio is 2.5, and the precipitation mixture is mixed with sodium carbonate to obtain Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zn 0.075 O 2 precursor.
[0324] S3: Put Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zn 0.075 O 2 The precursor was sintered in a muffle furnace and crushed to obtain Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zn 0.075 O 2 layered oxide; wherein the sintering conditions are: temperature: 850°C; time: 14h; heating rate: 5°C / min; oxygen atmosphere.
[0325] Embodiment A10
[0326] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Al 0.02 O 2 of layered oxides.
[0327] The positive electrode material preparation method comprises the following steps:
[0328] S1: According to Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Al 0.02 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 、Al 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0329] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.85 Ni 0.23 Mn0.42 Fe 0.28 Zn 0.04 Al 0.02 O 2 layered oxide; wherein the sintering conditions are: temperature: 850°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0330] Embodiment A11
[0331] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Sn 0.02 O 2 of layered oxides.
[0332] The positive electrode material preparation method comprises the following steps:
[0333] S1: According to Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Sn 0.02 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 SnO 2 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0334] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Sn 0.02 O 2 layered oxide; wherein the sintering conditions are: temperature: 850°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0335] Example A12
[0336] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ti 0.02 O 2of layered oxides.
[0337] The positive electrode material preparation method comprises the following steps:
[0338] S1: According to Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ti 0.02 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 、TiO 2 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0339] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ti 0.02 O 2 layered oxide; wherein the sintering conditions are: temperature: 850°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0340] Embodiment A13
[0341] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Mg 0.02 O 2 of layered oxides.
[0342] The positive electrode material preparation method comprises the following steps:
[0343] S1: According to Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Mg 0.02 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , MgO are ball-milled at a rotation speed of 500 rpm for 6 hours, and then sodium carbonate is added in proportion for mixing to obtain a precursor;
[0344] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Mg 0.02 O 2 layered oxide; wherein the sintering conditions are: temperature: 850°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0345] Embodiment A14
[0346] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ir 0.02 O 2 of layered oxides.
[0347] The positive electrode material preparation method comprises the following steps:
[0348] S1: According to Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ir 0.02 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 、IrO 2 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0349] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ir 0.02 O 2 layered oxide; wherein the sintering conditions are: temperature: 850°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0350] Embodiment A15
[0351] This embodiment provides a positive electrode material and a preparation method thereof. The positive electrode material includes a chemical formula of Na 0.85 Ni 0.23 Mn 0.42Fe 0.28 Zn 0.04 Ir 0.02 O 1.8 of layered oxides.
[0352] The positive electrode material preparation method comprises the following steps:
[0353] S1: According to Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ir 0.02 O 1.8 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 、IrO 2 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0354] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zn 0.04 Ir 0.02 O 1.8 layered oxide; wherein the sintering conditions are: temperature: 700°C; time: 20h; heating rate: 15°C / min; oxygen atmosphere.
[0355] Comparative Example A1
[0356] This comparative example provides a positive electrode material and a preparation method thereof. The positive electrode material comprises a chemical formula of Na 0.92 Ni 0.33 Mn 0.33 Fe 0.33 Zn 0.01 O 2 of layered oxides.
[0357] The positive electrode material preparation method comprises the following steps:
[0358] S1: According to Na 0.92 Ni 0.33 Mn 0.33 Fe 0.33 Zn 0.01 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0359] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.92 Ni 0.33 Mn 0.33 Fe 0.33 Zn 0.01 O 2 layered oxide; wherein the sintering conditions are: temperature: 900°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0360] Comparative Example A2
[0361] This comparative example provides a positive electrode material and a preparation method thereof. The positive electrode material comprises a chemical formula of Na 0.92 Ni 0.25 Mn 0.33 Fe 0.33 Zn 0.08 O 2 of layered oxides.
[0362] The positive electrode material preparation method comprises the following steps:
[0363] S1: According to Na 0.92 Ni 0.25 Mn 0.33 Fe 0.33 Zn 0.08 O 2 The molar ratio of metal elements contained is NiO, ZnO, Mn 2 O 3 , Fe 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0364] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.92 Ni 0.25 Mn 0.33 Fe 0.33 Zn 0.08 O 2 layered oxide; wherein the sintering conditions are: temperature: 900°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0365] Comparative Example A3
[0366] This comparative example provides a positive electrode material and a preparation method thereof. The positive electrode material comprises a chemical formula of Na 0.94 Ni0.33 Mn 0.33 Fe 0.33 O 2 of layered oxides.
[0367] The positive electrode material preparation method comprises the following steps:
[0368] S1: According to Na 0.94 Ni 0.33 Mn 0.33 Fe 0.33 O 2 The molar ratio of metal elements contained is NiO, Mn 2 O 3 , Fe 2 O 3 Ball milling was performed at a rotation speed of 500 rpm for 6 hours, and sodium carbonate was added in proportion for mixing to obtain a precursor;
[0369] S2: The precursor is sintered in a muffle furnace and crushed to obtain Na 0.92 Ni 0.25 Mn 0.33 Fe 0.33 O 2 layered oxide; wherein the sintering conditions are: temperature: 900°C; time: 12h; heating rate: 5°C / min; oxygen atmosphere.
[0370] Characterization of layered oxides and related performance tests in each example:
[0371] The layered oxides provided in the above-mentioned Examples A1 to A15 and Comparative Examples A1 to A3 were respectively tested for the relevant characteristics in Table 1 according to the following methods. The test results are shown in Table 1:
[0372] Element content detection method of layered oxide: Agilent ICP-OES730 was used to obtain inductively coupled plasma emission spectroscopy (ICP), and then the ICP results were used to calculate the content of each metal element, thereby calculating the mass percentage ratio of each component.
[0373] Single crystal morphology detection method: The scanning electron microscope (SEM) of the layered oxide provided in each embodiment is performed using the scanning electron microscope measurement method of GB / T 16594-1996 micrometer length. Among them, the electron microscope image of the layered oxide provided in Example A6 is as follows: Figure 1 shown.
[0374] Crystalline phase characterization method: The layered oxides were analyzed using an XRD diffractometer at a scanning rate of 0.5°C / min.
[0375] Dv50 detection method: Detect layered oxides according to the method steps in GB / T16418.
[0376] BET specific surface area detection method: Detect the specific surface area of layered oxides according to the method steps in GB / T19587-2017.
[0377] Compacted density test method: refer to GB / T24533-2019 standard test method for testing. For details, please refer to the following test steps:
[0378] (1) Use a clean soft cloth (paper towel) to wipe the upper and lower gaskets, top column and metal cylindrical sleeve of the compaction density meter. If necessary, wipe them with a soft cloth dipped in anhydrous ethanol and air dry them;
[0379] (2) Place the gasket, top column, metal cylindrical sleeve and pad in the order of the test on the digital thickness gauge and press the zero key;
[0380] (3) Remove the top column and upper gasket, weigh 1g of sample in the sleeve to an accuracy of 0.0001g, and record the weight as m;
[0381] (4) Slowly slide the gasket and the top column down from the hole, install them together with the pad on the compaction density meter, and tighten the pressure control knob;
[0382] (5) Shake the pressure bar and observe the value on the digital pressure gauge on the compaction density meter. Start the stopwatch after it reaches the specified value of 2200Ib; loosen the pressure control knob after 30 seconds to remove the pressure, lower the pad to a certain height, and then tighten the pressure control knob;
[0383] (6) Take out the top column, sleeve and film together with the pad, place them on the digital thickness gauge, and read the value on the digital thickness gauge within 10 seconds, which is recorded as H;
[0384] r = 10m / (S×H);
[0385] Then calculate the powder compaction density r of the sample according to the above formula r=10m / (S×H).
[0386] Where mm is the sample weight in grams (g); HH is the thickness of the sample after compaction in millimeters (mm); SS is the cross-sectional area of the top column in square centimeters (cm 2 ).
[0387] Charge / discharge gram capacity detection method: The charge / discharge gram capacity detection method of the layered oxide in the above application example is used for detection.
[0388] Table 1
[0389]
[0390]
[0391] From the test results of the relevant properties of the layered oxides provided in each embodiment in Table 1 above, it can be seen that the layered oxides with low zinc content provided in Examples A1 to A15 have similar crystal forms and particle sizes as those in Comparative Examples A1 to A3; however, the material compaction density of the layered oxides in Examples A1 to A15 is slightly higher than that in Comparative Examples A1 to A3. Further tests show that the specific surface areas of the layered oxide particles provided in Examples A1 to A15 are respectively 0.5 to 1.3 m 2 / g, further 0.6 to 0.9 m 2 The charge / discharge gram capacity of the layered oxides in Comparative Examples A2 to A3 is higher than that of the layered oxides in Examples A1 to A15. However, combined with the data in Table 3 below, it is known that due to the poor structural stability of Comparative Examples A2 to A3, their cycle performance is significantly lower than that of the layered oxides in Examples A1 to A15.
[0392] 2. Positive Electrode and Sodium Ion Battery Monomer Example
[0393] Example B1 to Example B15
[0394] Embodiments B1 to B15 provide a sodium ion battery cell, respectively. Each sodium ion battery cell includes an electrode assembly formed by a positive electrode sheet, a separator and a negative electrode sheet, and also includes an electrolyte.
[0395] The sodium ion battery cells in Examples B1 to B15 are assembled as follows:
[0396] Positive electrode sheet: Sodium ion positive electrode active material, conductive agent carbon nanotube, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an appropriate amount of solvent NMP in a weight ratio of 95:0.5:2:2.5 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of 13μm positive electrode collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained; wherein the sodium ion positive electrode active material is the positive electrode material in the above-mentioned Examples A1 to A15, respectively, and the positive electrode materials in the above-mentioned Examples A1 to A15 are prepared respectively. Among them, the conductive agent carbon nanotube content in Example B15 is 0 (the conductive agent is all conductive agent carbon black), that is, the conductive agent carbon nanotubes in Example B1 are replaced by conductive agent carbon black. Compared with the positive electrode sheet in Example B1, 0.5% of the carbon nanotube conductive agent in Example B1 is replaced by conductive agent carbon black, but the total content of the conductive agent contained in the positive electrode sheet in Example B1 is the same as the total content of the conductive agent contained in the positive electrode sheet of Example B1.
[0397] Negative electrode sheet: Add hard carbon, conductive agent SP, and CMC binder into deionized water in a weight ratio of 8:1:1, stir and mix thoroughly to form a uniform negative electrode slurry; evenly coat the negative electrode slurry on the surface of a 6μm copper foil, and obtain a negative electrode sheet after drying and cold pressing.
[0398] Electrolyte: In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate EC and diethyl carbonate DMC are mixed in a volume ratio of 1:1 to obtain an electrolyte solvent, and then sodium hexafluorophosphate and the mixed solvent are mixed to prepare an electrolyte with a sodium salt concentration of 1 mol / L.
[0399] Isolation membrane: Porous polyethylene (PE) membrane is used as the isolation membrane.
[0400] Battery assembly: The above-mentioned positive electrode sheets, separators and negative electrode sheets are stacked in order, so that the separator is located between the positive electrode sheets and the negative electrode sheets to play an isolating role, and the electrode assembly is obtained through the lamination process. Each electrode assembly is placed in an outer package, and after drying, the electrolyte is injected. After vacuum packaging, standing, forming, shaping and other processes, the sodium ion battery monomers in Examples B1 to B10 are obtained respectively. Among them, the sodium ion positive electrode active material contained in Example B1 is the positive electrode material in the above-mentioned Example A1, the sodium ion positive electrode active material contained in Example B2 is the positive electrode material in the above-mentioned Example A2, and so on. The sodium ion positive electrode active material contained in Example B15 is the positive electrode material in the above-mentioned Example A15.
[0401] Example B16 to Example B24
[0402] Embodiments B16 to B24 provide a sodium ion battery cell, respectively. Each sodium ion battery cell includes an electrode assembly formed by a positive electrode sheet, a separator and a negative electrode sheet, and also includes an electrolyte.
[0403] The sodium ion battery monomers in Examples B16 to B24 are prepared with reference to the sodium ion battery monomer in Example B3. The difference is:
[0404] In the sodium ion battery cells of Example B16 to Example B18, the content (CW) of the positive electrode active material layer contained in the positive electrode sheet of each sodium ion battery cell on a single surface of the current collector is controlled as shown in Table 2.
[0405] In the sodium ion battery cells of Example B19 to Example B21, the compaction density of the positive electrode active material layer contained in the positive electrode sheet of each sodium ion battery cell is controlled as shown in Table 2.
[0406] In the sodium ion battery monomers of Example B22 to Example B23, the content of carbon nanotubes contained in the positive electrode sheet of each sodium ion battery monomer is respectively controlled as shown in Table 2. Among them, the total content of the conductive agent contained in the positive electrode sheet of Example B22 to Example B23 is the same as the total content of the conductive agent contained in the positive electrode sheet of Example B1.
[0407] In the sodium ion battery cell of Example B24, the carbon nanotubes contained in the positive electrode sheet of the sodium ion battery cell are replaced with 1% carbon fibers, as shown in Table 2. The total content of the conductive agent contained in the positive electrode sheet of Example B24 is the same as the total content of the conductive agent contained in the positive electrode sheet of Example B1.
[0408] Comparative Examples B1 to B3
[0409] Comparative Examples B1 to B3 provide a sodium ion battery cell respectively. Each sodium ion battery cell includes an electrode assembly formed by a positive electrode sheet, a separator and a negative electrode sheet, and also includes an electrolyte.
[0410] The sodium ion battery monomers in Comparative Examples B1 to B3 are prepared with reference to the sodium ion battery monomer in Example B1. The difference is:
[0411] In the sodium ion battery cell of Comparative Example B1, the sodium ion positive electrode active material contained in the positive electrode sheet of the sodium ion battery cell is the sodium ion positive electrode material in Comparative Example A1, as shown in Table 1.
[0412] In the sodium ion battery cell of Comparative Example B2, the sodium ion positive electrode active material contained in the positive electrode sheet of the sodium ion battery cell is the sodium ion positive electrode material in Comparative Example A2, as shown in Table 1.
[0413] In the sodium ion battery cell of Comparative Example B3, the sodium ion positive electrode active material contained in the positive electrode sheet of the sodium ion battery cell is the sodium ion positive electrode material in Comparative Example A3, as shown in Table 1.
[0414] Related performance tests of the positive electrode sheets contained in the sodium ion battery monomers in each embodiment:
[0415] The positive electrode sheets contained in the sodium ion battery monomers provided in the above-mentioned Examples B1 to B24 and Comparative Examples B1 to B3 were respectively subjected to the relevant performance tests in Table 2 below according to the following methods. The test results are shown in Table 2:
[0416] Positive electrode slurry gel test method: After the positive electrode slurry used to prepare the positive electrode sheet contained in the sodium ion battery monomer of each of the above embodiments is placed at room temperature for 12 hours, the gelation of the positive electrode slurry is observed by naked eyes.
[0417] CW detection method: the electrode is punched and cut into 1540.25mm 2 The weight of the electrode is obtained by weighing and subtracting the weight of the aluminum foil, which is recorded as the weight of the active material layer / 1540.25mm 2 .
[0418] Positive electrode sheet compaction density test method: The compaction density of the positive electrode sheet can refer to the first discharge specific capacity and first charge and discharge efficiency test method of lithium manganese oxide, a positive electrode material of lithium-ion batteries, for details, see GB / T 39864-2021 standard or GB / T42161-2022. For details, please refer to the test steps of the following parameters:
[0419] The battery electrode that meets the processability requirements is obtained, and a positive electrode with a diameter of 14 mm is punched out using a punching machine. The mass m of the positive electrode is measured using an electronic balance and a desktop digital thickness gauge. c , thickness d c A sufficient number of aluminum foil substrates with a diameter of 14 mm were punched out using a punching machine, and the mass m of the aluminum foil substrates was measured using an electronic balance and a desktop digital thickness gauge. Al , thickness d Al ; Calculate the compaction density of the positive electrode according to the following formula:
[0420] Positive electrode compaction density
[0421] Where: c is the compaction density of the positive electrode, in grams per cubic centimeter (g / cm 3 );
[0422] m c is the mass of the positive electrode, in grams (g);
[0423] mAl is the mass of the aluminum foil substrate, in grams (g);
[0424] is the diameter of the positive electrode sheet, in millimeters (mm);
[0425] d c is the thickness of the positive electrode sheet, in micrometers (μm);
[0426] d Al is the thickness of the aluminum foil substrate, in micrometers (μm).
[0427] The charge gram capacity, discharge gram capacity and first efficiency of layered oxides are tested in accordance with the aforementioned national standards: GB / T39864-2021 or GB / T 42161-2022:
[0428] According to the battery treatment method in GB / T 39864-2021 or Section 7.4 of GB / T 42161-2022, place the assembled sodium ion button battery in a constant temperature box at 23°C ± 2°C, let it stand for 2 to 12 hours, and then charge and discharge it under the following conditions:
[0429] Charging: Constant current charging to 3.75V at 0.1C rate, then constant voltage charging, constant voltage charging medium current 0.05C; Discharging: Constant current discharge to 2.0V at 0.1C rate;
[0430] According to GB / T 39864-2021 or Section 7.5 of GB / T 42161-2022, the battery is charged and discharged for one cycle according to Section 7.4 of the sodium ion button cell assembled above, and the charge and discharge point capacity of the sodium ion button cell and the mass of the layered oxide in the corresponding sodium ion button cell are recorded, and the first discharge gram capacity and the first charge and discharge efficiency of the layered oxide are calculated.
[0431] The first discharge capacity in grams is calculated according to formula (4) in section 8.1 of GB / T 39864-2021 or GB / T 42161-2022, and the first charge and discharge efficiency is calculated according to formula (5) in section 8.2 of GB / T 39864-2021 or GB / T 42161-2022:
[0432] C=Q ID / m (4)
[0433] η = Q ID / Q IC ×100% (5)
[0434] In formula 4:
[0435] C——First discharge capacity in gram, in milliampere-hours per gram (mA.h / g);
[0436] Q ID —First discharge capacity in gram, in milliampere-hours per gram (mA.h / g);
[0437] m is the mass of the layered oxide in the tested sodium-ion button cell, in grams (g);
[0438] In formula 5:
[0439] η——First charge and discharge efficiency;
[0440] Q ID —First discharge capacity, in milliampere-hours (mA.h);
[0441] Q IC —The initial charging capacity in milliampere hours (mA.h).
[0442] The method for detecting the porosity of the pole piece is to detect it by gas replacement method, and refer to GB / T24586-2009 for specific steps. The specific steps of the method for detecting the porosity of the pole piece are as follows: the pole piece is immersed in ethyl methyl carbonate (EMC) for cleaning, and then tested by the method specified in GB / T24586-2009. The gas replacement method is used, combined with Archimedes' principle and Bohr's law, to accurately measure the true volume of the material being tested, which is the true volume of the sample, so as to obtain the porosity of the sample to be tested. Among them, the percentage of the pore volume in the pole piece to the total volume of the pole piece is the pole piece porosity, and the calculation formula is: porosity = (V-V0) / V×100%, where V0 is the true volume and V is the apparent volume.
[0443] Diaphragm resistance detection method: refer to GB / T 30835-2014 or T / CASAS 019-2021 method for detection; for the tester verification procedure, please refer to JJG 508-2004 method for detection. The four-probe method is used for detection: the electrode is immersed in ethyl methyl carbonate (EMC) for cleaning, and the method specified in GB / T 30835-2014 or T / CASAS 019-2021 is used for testing. Four copper plates with a length of 1.5cm, a width of 1cm, and a thickness of 2mm are fixed equidistantly on a line. The distance between the two middle copper plates is L (1cm to 2cm). The base material of the fixed copper plates is an insulating material. During the test, the lower end faces of the four copper plates are pressed on the electrode to be tested. The copper plates at both ends are connected to a DC current I. The voltage V is measured at the two middle copper plates. The I and V values are read three times, and the average value of I and V is taken. V / I is the electrode resistance at the test location.
[0444] Table 2
[0445]
[0446] Electrochemical performance test of sodium ion battery monomer in each embodiment:
[0447] The sodium ion battery monomers provided in the above-mentioned Examples B1 to B24 and Comparative Examples B1 to B3 were respectively subjected to the relevant electrochemical performance tests in Table 3 below according to the following methods. The test results are shown in Table 3:
[0448] Sodium ion battery monomer related performance testing method:
[0449] Cyclic DCR test: DCR test is carried out according to the normal temperature test method in the "High Power Lithium-ion Power Battery Performance Test Specification for HEV":
[0450] The battery cell to be tested is discharged at 1C constant current to the cut-off voltage (3.0V), and after being placed at 20±2℃ for 1h, it is charged at 1C current for 18min, the SOC is adjusted to 30%, and placed for 1h, and then charged at 3C for 1.5min, and placed for 1h, and then discharged at 9C for 0.5min, and placed for 1h, and then charged at 1C for 6min, and the SOC is adjusted to 40%, and placed for 1h. This cycle is repeated until the SOC is 70% and the DCR value is obtained by the calculation formula.
[0451] Energy density: Measure the discharge energy S0 of each battery cell when it is charged at a rate of 0.33C to a voltage of 4.2V at room temperature, and then discharged at a rate of 0.33C to a voltage of 2.0V. Then measure the mass M of the battery cell corresponding to S0, and calculate the mass energy density of the battery cell according to the S0 / M formula.
[0452] Cycle retention rate (%): At 25°C, the secondary battery is charged to 3.85V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage of 3.85V, and then discharged to 1.5V at a constant current of 1C. This is a charge and discharge cycle. Taking the capacity of the first discharge as 100%, calculate the capacity retention rate of the battery after 1000 cycles. Capacity retention rate (%) after 1000 cycles of the battery = discharge capacity of the 1000th cycle / capacity of the first discharge × 100%.
[0453] Table 3
[0454]
[0455] It can be seen from the data in Table 2 and Table 3 that in the sodium ion battery of the present application, the compaction density of the positive electrode active material layer contained in the positive electrode sheet in the sodium ion battery monomer provided by Examples B1 to B24 can reach 2.8 to 3.4 g / cm 3 , the CW of the positive electrode active material layer can reach 260~350mg / 1540.25mm 2Furthermore, while controlling the CW and compaction density of the positive electrode active material layer, the porosity of the positive electrode active material layer is 40% to 65%, and the membrane resistance is 0.5 to 5 mΩ. Specifically, the porosity and membrane resistance of the positive electrode active material layer can be adjusted according to the CW and compaction density of the positive electrode active material layer and the conductive agent contained therein.
[0456] It can be seen from Example B1 to Example B8 in the comparison table that as the content of zinc in the layered oxide shown in the chemical formula (I) gradually increases, the energy density of the battery cell of the sodium ion battery monomer gradually increases. Of course, the overall trend of the cycle performance of the corresponding sodium ion battery monomer is a downward trend. In the layered oxide shown in the chemical formula (I), as the zinc content increases, it can increase the gram capacity of the layered oxide, but it is not conducive to the structural stability of the layered oxide, so that the cycle performance of its reversible capacity is reduced. However, compared with Comparative Examples 1 and 2, it can be seen that the zinc element is controlled in an appropriate range and satisfies the appropriate stoichiometric ratio of Zn to Ni and Mn. The layered oxide shown in the chemical formula (I) can effectively take into account both high gram capacity and good reversible capacity cycle stability.
[0457] It can be seen from Example B3 and Example B10 to Example B14 in the comparison table that the type of doped metal element contained in the layered oxide represented by chemical formula (I) also has a certain influence on the specific capacity and structural stability of the layered oxide. Therefore, the doped metal element represented by M participates in the disordered arrangement of metal elements in the transition metal layer contained in the layered oxide, and can contribute to the specific capacity and / or structural stability of the layered oxide.
[0458] Comparing Example B14 and Example B15, the type of conductive agent contained in the positive electrode active material layer contained in the positive electrode sheet has a certain influence on the capacity of the positive electrode sheet. When the conductive agent contains linear carbon nanotubes, the energy density of the corresponding sodium ion battery cell is higher than that of Example B15.
[0459] Comparing Examples B1 to B15 with Comparative Examples B1 to B3, when the layered oxide zinc content is too low, such as in Comparative Examples B1 and B3, not only does it result in a significant decrease in the energy density of the sodium ion battery monomer, but it also significantly reduces the cycle retention rate of the sodium ion battery monomer. When the layered oxide zinc content is too high, such as in Comparative Example B2, although the energy density of the sodium ion battery monomer can be maintained without a significant decrease, the cycle retention rate of the sodium ion battery monomer is significantly reduced. It can be seen that the zinc element and other metal element types and the content of each metal element in the layered oxide shown in chemical formula (I) can significantly affect the disordered arrangement of the metal elements in the transition metal layer contained in the layered oxide, thereby significantly affecting the comprehensive performance of the gram capacity and cycle stability of the layered oxide.
[0460] It can be seen from this that the layered oxide of the embodiment of the present application controls the zinc element within a suitably low content range, and controls the content of zinc element and metal elements such as Ni, Fe, and Mn, so that the transition metal layer contained in the layered oxide of the embodiment of the present application has a specific arrangement, and on the basis of effectively improving the gram capacity of the layered oxide, it also takes into account and balances the structural stability of the layered oxide, thereby improving the cycle performance of the layered oxide and the sodium ion battery. It also shows that in the layered oxide of the embodiment of the present application, it is not that the higher the zinc content, the higher the gram capacity of the layered oxide and the better the cycle performance, but when the zinc content exceeds a certain amount, its gram capacity does not continue to increase, and it is not good for the structural stability of the layered oxide, so that the cycle performance of the layered oxide is reduced.
[0461] In addition, it can be seen from the data in Table 3 that the cell DCR variation range of the sodium ion battery monomers in Examples B1 to B24 is not large, and the cell DCR difference of each sodium ion battery monomer in Examples B1 to B24 is in the range of 0mΩ to 0.8mΩ. Moreover, the cell DCR of the sodium ion battery monomers in Examples B1 to B24 is significantly lower than the cell DCR value of the sodium ion battery monomers in Comparative Examples B1 to B3. Therefore, the layered oxide represented by chemical formula (I) controls the zinc contained within the content range of chemical formula (I). On the one hand, on the basis of improving the stability of the layered oxide structure by controlling the low zinc content and adjusting the arrangement of other metal elements in the transition metal layer, it can also stabilize the transition metal interlayer channel, improve the sodium ion transmission rate, and improve the DCR growth of the battery cell.
[0462] Further, the positive electrode slurries in Examples B1 to B24 are compared with those in Comparative Examples B1 and B3, and it can be seen that the gelation of the positive electrode slurries in Examples B1 to B24 is significantly lower than that in Comparative Examples B1 and B3. Therefore, the layered oxides in the embodiments of the present application control the zinc element within a properly low content range, and on the basis of effectively improving the gram capacity and cycle performance of the layered oxides, the processing performance of the layered oxides is also improved.
[0463] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A positive electrode material, characterized in that: It includes layered oxides shown in the following chemical formula: So q Ni x Mr y Feb z Zn p M i O j ; Among them, 0.8≤q≤1, 0.1≤x≤0.3, 0.2≤y≤0.5, 0.2≤z≤0.35, 0.02≤p≤0.075, 0≤i≤0.1, 1.8≤j≤2, and x+y+z+p+i≤1; M is an active and / or inert doping metal element.
2. The positive electrode material according to claim 1, characterized in that At least one of q, x, y, z, p and i is in the following value range: 0.15≤x≤0.25, 0.25≤y≤0.45, 0.25≤z≤0.32, 0.04≤p≤0.07, 0≤i≤0.
05.
3. The positive electrode material according to claim 1 or 2, characterized in that: The stoichiometric ratio of the total stoichiometric amount of the Ni element, the Mn element, the Fe element, the Zn element and the doping metal element to the Na element is 1:(0.8-1), and can be optionally 1:(0.83-0.95).
4. The positive electrode material according to any one of claims 1 to 3, characterized in that: The stoichiometric ratio of the Zn element to the Ni element is 1:(3-15), and can be optionally 1:(3.1-11); and / or The stoichiometric ratio of the Zn element to the Mn element is 1:(4-25), and can be optionally 1:(5-15).
5. The positive electrode material according to any one of claims 1 to 4, characterized in that: The doping metal element includes at least one of V, Ca, Cr, Al, Sc, Sn, Sb, Zr, Nb, Ti, Mg, Cu, Ru, and Ir.
6. The positive electrode material according to any one of claims 1 to 5, characterized in that The above-mentioned lamellar compound inclusive Na 0.89 Ni 0.23 Mn 0.45 Fe 0.3 Zinc 0.02 O2, Na 0.89 Ni 0.23 Mn 0.44 Fe 0.3 Zinc 0.03 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Cu 0.02 O2, Na 0.89 Ni 0.23 Mn 0.42 Fe 0.3 Zinc 0.05 O2, Na 0.89 Ni 0.23 Mn 0.41 Fe 0.3 Zinc 0.06 O2, Na 0.89 Ni 0.23 Mn 0.42 Fe 0.28 5Zn 0.065 O2, Na 0.89 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.07 O2, Na 0.9 Ni 0.23 Mn 0.4 Fe 0.3 Zinc 0.075 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 V 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Cr 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Al 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Sc 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Sn 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Sb 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Zr 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Nb 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Ti 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Mg 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Ru 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Ir 0.02 O2, Na 0.85 Ni 0.23 Mn 0.42 Fe 0.28 Zinc 0.04 Ir 0.02 O 1.8 Very little in the middle.
7. The positive electrode material according to any one of claims 1 to 6, characterized in that: The layered oxide includes at least one of the following features (1) to (3): (1) The crystal structure includes an O3 phase layered metal oxide, and the O3 phase layered metal oxide accounts for more than 95% of the total weight of the layered oxide; (2) Dv50 particle size is 3 to 11 μm, and can be 4 to 8 μm; (3) It includes a single crystal, wherein the single crystal has a flat morphology.
8. The positive electrode material according to claim 7, characterized in that: The single crystal has the following characteristics: (1) The ratio of length, width and thickness is 1-8:1-5:0.5-2.5, which can be 2-6:2-4:1-2; (2) Length is 1 to 8 μm, and can be 2 to 6 μm; (3) Width is 1 to 5 μm, and can be 2 to 4 μm; (4) The thickness is 0.5 to 2.5 μm, and can be optionally 1 to 2 μm.
9. The positive electrode material according to any one of claims 1 to 7, characterized in that: The layered oxide includes at least one of the following features (1) to (3): (1) The compaction density under 2 tons of pressure is 2.8 to 3.1 g / cm 3 , optional: 2.9~3.09g / cm 3 ; (2) The compaction density under 3 tons of pressure is 3.1-3.3 g / cm 3 , can be selected as 3.15~3.28g / cm 3 ; (3) Specific surface area is 0.5 to 1.3 m 2 / g, optional range is 0.6~0.9m 2 / g.
10. The positive electrode material according to any one of claims 1 to 9, characterized in that: The layered oxide comprises at least one of the following (1) to (3) at 1.5 to 4.2 V and 0.1 C: (1) The charging capacity is 164-174 mAh / g, and can be selected as 165-172 mAh / g; (2) The discharge capacity is 158-165 mAh / g, and can be selected as 160-163 mAh / g; (3) The initial efficiency is 92-98%, which can be selected as 92-95%.
11. A method for preparing a positive electrode material, characterized in that: The steps include: Provide Na q Ni x Mn y Fe z Zn p M i O j Precursor of The precursor is sintered to obtain a product having a chemical formula of Na q Ni x Mn y Fe z Zn p M i O j Layered oxides; Among them, 0.8≤q≤1, 0.1≤x≤0.3, 0.2≤y≤0.5, 0.2≤z≤0.35, 0.02≤p≤0.07, 0≤i≤0.1, 1.8≤j≤2, and x+y+z+p+i≤1; M is an active and / or inert doping metal element.
12. The preparation method according to claim 11, characterized in that: The doping metal element includes at least one of V, Ca, Cr, Al, Sc, Sn, Sb, Zr, Nb, Ti, Mg, Cu, Ru, and Ir; and / or At least one of q, x, y, z, p and i is in the following value range: 0.15≤x≤0.25, 0.25≤y≤0.45, 0.25≤z≤0.32, 0.04≤p≤0.07, 0≤i≤0.
05.
13. The preparation method according to claim 11 or 12, characterized in that: The sintering process includes at least one of the following conditions (1) to (4): (1) The temperature is 700-980°C, and can be 750-950°C; (2) The time is 4 to 20 hours, and can be 6 to 12 hours; (3) The temperature is raised to the sintering temperature at a heating rate of 2 to 15°C / min.
14. The preparation method according to any one of claims 10 to 12, characterized in that: The Na q Ni x Mn y Fe z Zn p M i O j The precursor is prepared according to a method comprising the following steps: According to Na q Ni x Mn y Fe z Zn p M i O j The precursor is obtained by solid phase mixing a sodium source, a nickel source, a manganese source, an iron source, a zinc source and a doping metal element source represented by M according to the stoichiometric ratio of the elements contained therein; and / or The Na q Ni x Mn y Fe z Zn p M i O j The precursor is prepared according to a method comprising the following steps: According to Na q Ni x Mn y Fe z Zn p M i O j A soluble nickel source, a soluble manganese source, a soluble iron source, a soluble zinc source and a soluble doping metal element source represented by M are prepared into a mixed solution according to the stoichiometric ratio of the elements, and at least one of a precipitant and a complexing agent is added to perform a coprecipitation treatment to obtain a precipitated mixture; The precipitation mixture is mixed with a sodium source to obtain the precursor.
15. A positive electrode, comprising a positive electrode active material, characterized in that: The positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 10 or the positive electrode material prepared by the preparation method according to any one of claims 11 to 14.
16. The positive electrode according to claim 15, characterized in that: The content of the positive electrode active material on the single surface of the current collector is 260-350 mg / 1540.25 mm 2 , optional: 280~320mg / 1540.25mm 2 ; and / or The compaction density of the positive electrode is 2.8 to 3.4 g / cm 3 , can be selected as 2.9~3.2g / cm 3 .
17. The positive electrode according to claim 15 or 16, characterized in that: The porosity of the positive electrode active material layer is 40% to 65%, and can be 45% to 60%; and / or The positive electrode is a pole piece, and the membrane resistance of the pole piece is 0.5 to 5 mΩ, and can be optionally 0.5 to 3 mΩ.
18. The positive electrode according to any one of claims 15 to 17, characterized in that: The positive electrode is a pole piece, and the ratio of the thickness from one surface of the pole piece to the other opposite surface to the thickness of the current collector is 6 to 15:1, and can be optionally 8 to 14:
1.
19. The positive electrode according to any one of claims 15 to 18, characterized in that: The conductive agent contained in the positive electrode active material layer includes a linear conductive agent.
20. The positive electrode according to claim 19, characterized in that: The mass content of the linear conductive agent in the positive electrode active material layer is 0.1% to 2.5%, and can be 0.2% to 0.8%; and / or The aspect ratio of the linear conductive agent is 40 to 3000:1, and can be selected as 50 to 2500:1; The length of the linear conductive agent is 0.5 to 5 μm, and can be 0.5 to 2 μm; and / or The diameter of the linear conductive agent is 2 to 10 nm, and can be 3 to 7 nm; and / or The linear conductive agent includes at least one of carbon nanotubes, carbon fibers, and conductive oxide nanowires.
21. A sodium battery, characterized in that: The positive electrode comprises the positive electrode according to any one of claims 15 to 20.
22. An electrical device, characterized in that: Including the sodium battery as claimed in claim 21.
Citation Information
Patent Citations
Low-nickel high-energy-density O3 type sodium ion battery positive electrode material and preparation method thereof
CN116544408A
High-entropy doped O3 phase layered oxide and preparation method thereof, sodium ion battery positive electrode material and battery
CN116605918A
Cited By
Positive electrode material and preparation method therefor, positive electrode, sodium battery and electric device
EP4787466A1
Positive electrode material and preparation method therefor, positive electrode, sodium battery and electric device
WO2025066099A1